Teacher reflections and praxis: a case study of Indian teachers of English as a foreign language - Makarani, Sakilahmed A. R. (University of Hawai'i at Mānoa, 2012)
This case study engaged Gujarati English as Foreign Language (EFL) teachers in video-based reflection with the goal of increasing their reflective abilities and uncovering their understandings about reflective teaching practices in the Indian pedagogical and cultural context. The study aimed to explore, and gain a deeper understanding of how structural, institutional, and social dynamics of the larger socio-political cultural context of India affected the classroom teachers' thinking and their teaching practices. It was hoped that not only would the Gujarati teachers demonstrate an ability to reflect on their practice, but that they would also engage in a critical examination of the factors that impacted their context. The computer-based qualitative data analysis software, Atlas.ti, was used to analyze data using a grounded theoretical approach. The findings indicated that participants successfully engaged in reflection about their teaching using video as the tool for their professional development. Initially teacher participants had mixed feelings about recording and watching videos of their classroom instruction; however, teacher participants later enjoyed the experience, explicitly stating that such reflection helped them. The study also revealed that teacher participants perceived parental, social, institutional, and economic factors as influences on their students' learning, however these were simply identified as problems or conditions without any type of deeper critical analysis. Further, it was found that the teachers did not reach a critical level of reflection, nor did they consider taking action to address fundamental contextual issues. While this study showed that teacher reflection using digital video recordings of classroom practice can be a productive approach to meaningful teacher reflection in India, the study also demonstrated that teachers need specific exposure to deeper critical pedagogical thinking to go beyond simply identifying or blaming the social or economic issues embedded in their context. The study concludes with recommendations on how to reach critical teacher reflection. It is hoped that this case study will add to the growing body of research literature related to teacher self-reflection as a means to improving teaching practice and preparing teachers to take on social challenges in the Indian context. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Case Studies; Computer Software; Cultural Context; ERIC, Resources in Education (RIE); Economic Factors; English (Second Language); Foreign Countries; Grounded Theory; India; Indians; Language Teachers; Qualitative Research; Reflective Teaching; Second Language Instruction; Second Language Learning; Social Influences; Teacher Attitudes; Teaching Methods; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096525; __finaldtb

The effectiveness of integrating interactive technology in reading comprehension: A case study of Jamaica's grade school - Iyare, Ngozi F.; James, Julia; Amonde, Tom M. (Journal of Information Technology Education: Research, 2018)
Aim/Purpose: There is growing number of countries embarking on large-scale, government-supported initiatives (e.g., Antigua & Barbuda, Australia, Brazil, India, Iran, Jamaica, Kazakhstan, Pakistan, Russia, Turkey, and the United Arab Emirates) to distribute tablet devices to students in the K-12 schooling sector. The review of the government-supported initiatives concluded that the majority of these initiatives have been driven not by educational frameworks or research-based evidence but by the tablet hype. The goal of this study is to provide research-based evidence by investigating if the learning experience for grade-three learners with interactive technology improves knowledge and skills in reading comprehension compared to learning in the traditional chalk and talk environment. Background: Prior studies provided limited evidence based mainly on data from developed countries about the influence of the use of interactive technology on reading comprehension at lower grade school level. Methodology: Employing a mixed-method case study research approach, this study aims to investigate the effects of integrating interactive technology in reading comprehension and examine the perspectives of students. This case study employed a sample of 30 public school third-grade students located in a relatively poor residential area in St Catherine, Jamaica as well as the two classroom teachers. Thirty students were divided into two groups -- an experimental group, which included 16 participants and a control group, which included 14 participants. The intervention program was carried out over a period of eight weeks. Contribution: This study has provided (a) additional data to show evidence for the effectiveness of interactive technology in reading comprehension and (b)research based evidence for the distribution of computer devices to students in the K-12 schooling sectors. Findings: We found empirical support for the positive effects of technology-based approaches for addressing reading comprehension and vocabulary skills. Our results were based on the pre-test and post-test assessments. Additional data was collected using a survey questionnaire which was given to the students before and after the intervention. The change from pretest to posttest was significantly different between the two groups as measured by the Mann Whitney U test. Recommendations for Practitioners: The empirical support for the effects of technology-based approaches for addressing reading comprehension and vocabulary skills identified in this study will assist teachers with strategies and programs that should improve students' motivation as well as their grades. Recommendation for Researchers: For future studies, we recommend focusing on a longer intervention period and using a larger sample size that would likely yield more definitive and generalizable results.
Keywords: Case Studies; Control Groups; Conventional Instruction; ERIC, Current Index to Journals in Education (CIJE); Elementary Education; Elementary School Students; Experimental Groups; Foreign Countries; Grade 3; Instructional Effectiveness; Jamaica; Mastery Learning; Outcomes of Education; Reading Comprehension; Reading Improvement; Reading Instruction; Teaching Methods; Technology Integration

The Impact of ICT as Another Route to Overcome Learning Barriers for Students with SEN: A Case Study in an Egyptian Context - Al-Gawhary, Wedad; Kambouri, Maria (International Association for the Development of the Information Society, 2012)
The purpose of this case study was to measure the impact of using ICT in Individual Learning Programmes of students with learning disabilities. Twenty five students and thirteen teachers took part in the research which was based on classroom observations. The Kappa coefficient was employed as a measure to statistically quantify the students' acquisition and progress in learning computer and literacy skills through raters' observations. A high correlation between Keyboard, PowerPoint, and literacy skills (writing, reading, and maths) was revealed suggesting the significance and impact of keyboard training as an essential component towards achieving educational objectives. Moreover, thematic analysis of the teachers' interviews provided a further dimension for understanding factors influencing the ICT integration process. These results further confirmed the positive impact of computer skills training on the students' learning experience which also revealed a strong belief in the right of every child to all learning opportunities, particularly ICT regardless of his/her abilities.(Contains 2 tables.) [For the complete proceedings, "Proceedings of the International Association for Development of the Information Society (IADIS) International Conference on Cognition and Exploratory Learning in Digital Age (CELDA) (Madrid, Spain, October 19-21, 2012)," see ED542606.]
Keywords: Autism; Barriers; Case Studies; Cerebral Palsy; Communications; Computer Literacy; Computer Mediated Communication; Computer Software; Down Syndrome; Foreign Countries; Heterogeneous Grouping; Information Technology; Interrater Reliability; Mixed Methods Research; Semi Structured Interviews; Semitic Languages; Special Needs Students

A case study of using an online community of practice for teachers' professional development at a secondary school in China - Wang, Qiyun; Lu, Zhiping (Learning, Media and Technology, 2012)
In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers liked using the online community as they could gain subject knowledge and could obtain support from peers, share experiences and get feedback, and exchange resources. Also, online entries confirmed that transformational changes in teaching pedagogy and students' learning activities occurred along the time. However, certain teachers did not participate in the online community frequently. This paper describes the context of the case study, design dimensions of the online community, teachers' positive perceptions on using the online community, and transformational changes. Also, strategies for promoting effective use of the online community are discussed and follow-up studies to address the challenges involved in this study are proposed. [PUBLICATION ABSTRACT]
Keywords: Case Studies; China; Communities of Practice; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational Practices; Electronic Learning; Electronic Mail; Foreign Countries; Interviews; Learning; Lesson Plans; Mail Surveys; Online instruction; Participant Satisfaction; Pedagogy; Polls & surveys; Professional Development; Professional development; Secondary Education; Secondary School Teachers; Secondary school teachers; Teacher Surveys; Teaching Methods; Technology Uses in Education; Transformative Learning; __:import:01; __:match:final; __:matched; __:study_id:2096477; __finaldtb; community of practice; lesson planning; professional development; reflection; technology

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Understanding language teachers' practice with educational technology: A case from China - Li, Li (System, 2014)
This article explores how eight secondary school teachers integrated educational technology into English language teaching in Beijing, China and considers their views of the factors influencing technology use. Analysing data from classroom recordings and follow-up interviews, this study revealed that PowerPoint was the most frequently used technological application in the classroom, while the internet and other technological tools were also used by the teachers. They employed educational technology for different pedagogical purposes, including addressing professional needs in improving teaching, designing materials and conducting professional development. Teachers also claimed that they used technology to address learners' needs, such as improving engagement, enhancing language acquisition, facilitating understanding and establishing a context for language use. The study identified four important factors in influencing teachers' use of technology, including sociocultural contexts, teachers' beliefs, access to resources, and technology competence and confidence. This study suggests that a critical reflective approach is useful in assisting teachers to understand their needs and pedagogical beliefs concerning technology use. Ongoing professional development is also valuable in promoting teachers' technology competence and confidence, thereby improving the use of technology in their teaching.
Keywords: Case study; China; Socio-cultural context; Teachers' perceptions; Technology use

School-based professional development in a developing context: Lessons learnt from a case study in Zambia - Haßler, Björn; Hennessy, S.; Cross,, A. (Professional Development in Education, 2014)
This paper reports on the development and outcomes of the second phase of OER4Schools, a school-based professional development programme supporting interactive forms of subject teaching in conjunction with Open Educational Resources (OER) and technology in Zambian primary schools. We worked with partners to identify the needs of school-based continuing professional development adapted to the local context; the programme was based on participatory, collaborative and inquiry-based pedagogies for both classroom learning and teacher development. We worked over a one-year period with four experienced teachers in two basic (primary) schools serving disadvantaged communities. Data were collected from observations, interviews, surveys, lesson planning/review meetings and team workshops. All participants integrated OER and technology into mathematics and science lessons and developed more interactive practices, including collaborative learning. Professional dialogue, quality conversations, reflective practice, cultural sensitivity, peer learning and cooperation were pivotal mechanisms through which teachers shifted their focus from teaching (and teacher exposition) to student learning. Seeing students as capable individuals, teachers raised their expectations and developed insight into interactive practices such as group work, providing meaningful opportunities for student collaboration and active learning by all.
Keywords: Author:Haßler; Open Educational Resources; Zambia; digital technology; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; reflective practice; school-based professional development; sub-Saharan Africa

Digital storytelling and reflection in higher education: a case of pre-service student teachers and their lecturers at a university of technology - Ivala, Eunice; Gachago, Daniela; Condy, Janet; Chigona, Agnes (Journal of Education and Training Studies, 2014)
Employers in South Africa are calling for students graduating from higher education institutions (HEIs) to exhibit the capacity for reflection. However, many tertiary institutions fall short in allowing opportunities for reflection. As a result, HEIs are grappling to find ways of fostering reflection amongst their students. This paper argues that digital storytelling if implemented properly is one of the ways which can be used to help HEIs in this accomplishment. It documents results of production of digital stories by 29 final-year pre-service student teachers at the Cape Peninsula University of Technology (CPUT), South Africa, as part of their assessment in their professional development course. The study was informed by structuration theory and levels of reflection and cognitive processing to help the researchers understand the potential of digital storytelling in enhancing reflection. Qualitative methods of collecting data were utilized. Focus group interviews were conducted with the students and their facilitators to elicit whether production of digital stories led to reflection. Findings showed that the production of digital stories promoted the three levels of reflection and thus deep learning and higher-order thinking skills.
Keywords: Case Studies; Cognitive Processes; College Faculty; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Focus Groups; Foreign Countries; Higher Education; Personal Narratives; Postsecondary Education; Preservice Teachers; Professional Development; Qualitative Research; Reflection; Skill Development; South Africa; Story Telling; Teaching Methods; Technology Uses in Education; Video Technology; __:import:02; __:match:final; __:matched; __:study_id:2096367; __finaldtb

Policy adoption of learner-centred pedagogy in Rwanda: A case study of its rationale and transfer mechanisms - van de Kuilen, Hester S.; Altinyelken, Hulya Kosar; Voogt, Joke M.; Nzabalirwa, Wenceslas (International Journal of Educational Development, 2019)
This study explores why and how learner-centred pedagogy (LCP) as a policy has been adopted in Rwanda, despite ample evidence of the failure of LCP in developing countries. The case of Rwanda, as a late adopter, shows that at this stage of pedagogy diffusion the influence of global mechanisms and actors has been amplified. This study draws upon interviews with key stakeholders and relevant documents during the 2011–2016 period. The transfer process is examined by analysing the rationale offered and mechanisms deployed by the Rwandan government and aid agencies.
Keywords: Competence-based education; Curriculum reform; Education policy transfer; Learner-centred pedagogy; Policy adoption; Rwanda

Using Tactile Letters As An Assistive Technology In Teaching Alphabet For Dyslexic Children: A Case Study - Mohamed, Mariam; Tan, Abdullah (13th International Scientific Conference "eLearning and Software for Education", 2017)
Dyslexia is a specific learning disability characterized by difficulties with accurate and/or fluent word recognition, poor spelling and poor decoding abilities. Dyslexic children are having language learning disorder and makes them difficult mastering the skill to read, spell and write. This research explores the design from tactile letters to mobile application that support alphabet recognition and early reading acquisition in children, particularly dyslexic children. The research design of this study is qualitative based on case study methodology. The approach of tactile letters and mobile application which could foster learning and help dyslexic children to improve some of their fundamental skills, such as recognizing alphabet and pronunciation. This study describes the design and evaluation of an assistive technology based in lieu of teaching alphabet for dyslexic children. The combination of tactile letters and mobile application may be the ground-breaking of stimulating and interactive experience for children that could encourage the learning process.

Teachers’ perspectives on their use of ICT in teaching and learning: A case study - Kafyulilo, Ayoub; Keengwe, Jared (Education and information technologies, 2014)
This article presents the perspectives of science and mathematics teachers on their use of information and communication technology (ICT) in teaching and learning in Tanzania. The findings show that few teachers used computers for teaching and learning purposes while majority of them used computers for administrative purposes. Additionally, teachers were found to have limited confidence in using technology to facilitate specific concepts or skills, to support creativity, and to support students to learn complex concepts. Therefore, it is suggested that schools explore strategies ICT integration strategies that focus more on making a shift from teaching technology or using technology for administrative purpose to appropriate pedagogical uses that could enhance student learning.
Keywords: Case studies; Communication; Computer Appl. in Social and Behavioral Sciences; Computer Science; Computers and Education; Education; Educational Technology; Information Systems Applications (incl.Internet); Information technology; Learning; Learning strategies; Mathematics; Pedagogy; Science; Student Learning; Study and teaching; Teacher attitudes; Teachers; Teaching; Technology Integration; Technology application; Training; User Interfaces and Human Computer Interaction

Female Teachers' Perceptions of Quality Education for Adolescent Girls in Rural Bangladesh: A Case Study - Rahim, N (2017)
The education of adolescent girls in Bangladesh must be pursued with the right combination of technology, practicality, and cultural sensitivity to achieve, among other objectives, the objectives of Millennium Development Goals (MDGs). The problem this study address is despite the availability of mobile-based curricula, such as video, mobile phones, and Short Message System (SMS) technology, female teachers in rural areas are not trained to plan and deliver curricula using mobile platforms. The purpose of this qualitative single case study is to explore barriers associated with female teachers’ training of the use of mobile-based technology in rural areas in Bangladesh. The sample is, randomly selected a minimum of eight local female teachers who had been teaching at least for two years in a rural school in Bangladesh. The data were collected to determine the local teachers’ perception on establishing quality education through virtual (email, mobile phone, IMO, zoom or Skype) interviews administered to these 8 local female teachers. The researcher gathered data from the local female teachers’ point of view based on their motivation to receive training in becoming proficient in English and the use of mobile technology in teaching. A content analysis tool was used for analyzing, interpreting, coding, and categorizing textual data where themes identified based on a comprehensive classification system. The findings from the data analysis would aid schools in recruiting, training, and retaining local female teachers to provide quality education to the adolescent girls. The data from the single case study provided information as to the use of mobile and web technologies in teaching and learning while local female teachers gain proficiency in the English language. The insight gained from this single case study may help develop future technology budgets, infrastructure, and curriculum needs. The findings from research revealed that the rural Bangladeshi school teachers noted that there is limited use of videos in the classrooms for teaching due to, in some parts, the lack of training by school administrators on strategies to use videos in their teaching. Some barriers to the use of videos is due to the lack of Internet connection, the lack of knowledge on the proper use of videos in their teaching, and the lack of administrators’ support for this type of curriculum change in the schools.

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

Performance Oriented Information and Communication Technology (ICT): Model for Education Purpose in Pakistan. A Bahawalpur District Case Study - Qadri, Salman; Shah, Rehan Ali; ul Rehman, Muzammil; Ullah, Saleem; Shah, Ali Nawaz; Ali, Muhammad Zaman; Ahmed, Muhammad Munawer (International Journal of Computer Science and Network Security, 2017)
Information technology brought a dramatic change in our society. In third world countries such as Pakistan is also trying to get involve this technology in every field of life. In this decade, information technology is being used in several disciplines such as education, health, agriculture and business etc. It has given a positive impact on all of these disciplines especially E-banking, E-learning and E-commerce etc. This study focuses the implementation of information and communication technology (ICT) framework to boost the progress of different less develops areas in Pakistan. This study also describes the complete methodology with all of its benefits and constraints on implementation and also proposed a framework to improve the efficiency and accuracy in education department in primary to higher level in Bahawalpur district and its five sub districts (tehsil) and also take the case study of The Islamia University Bahawalpur within city sub campuses by utilizing the successful implementation of information and communication technology for the betterment of education.
Keywords: E-Classes; ICT Infrastructure; IT-Centers; Information and Communication Technology; integration; teachers; ⛔ No DOI found

Blended learning implementation in secondary education for girls: case study Tatweer project Saudi Arabia - Bukhari, Eman Gasim (International Journal of Academic Research and Reflection, 2016)
Blended learning (BL) has been the subject of much research recently, and the present research adds to this growing body of knowledge as the first substantial study on BL in secondary education for girls in Saudi Arabia. Based on field work comprising interviews and questionnaires this research reports the results of an exploratory, empirical case study of a large-scale programme (Tatweer project) for the introduction of blended learning into 25 traditional secondary girls' schools in Saudi Arabia. Adopting the interpretive research paradigm the objective of the study is to gain rich insight into blended learning guided by the effect of BL on female education. The study demonstrates a number of positive effects of BL on students' engagement and self-development, however, problems with the workloads of students and the failure of teachers to integrate face-to-face learning with e-learning are also observed. Throughout the research Sharpe et al.'s (2006) 8-dimensional framework of BL is applied in a new way to assess the implementation level of BL. This results in the recommendation to extend this framework with an ethical dimension. Further recommendations of the work are to actively seek feedback from key stakeholder groups during BL implementation, to use BL for teacher training in BL, and to measure performance indicators like students' workloads during the transition of traditional schools to BL.
Keywords: ⛔ No DOI found

Integration of ICT in Education in a Secondary School in Kenya: A Case Study - Kisirkoi, Florence (Literacy Information and Computer Education Journal, 2015)
Amidst reports that there was very little integration of Communication Information Technology (ICT) in curriculum delivery in many secondary schools in Kenya, it was reported that one secondary school was using ICT in instruction and practicing learner centered instructional approaches and there was improved learning outcomes. The school’s mean score in the Kenya Certificate of Secondary Education had improved from 6.2 to 8.4 between 2007 and 2013. This study teacher computer literacy levels, motivation for integration, perceived reason for the intervention and the impact on teaching and learning. A case study was conducted and observation and interview schedules were used to collect data. The study population was the 535 students and the 28 teachers in the school. Simple random sampling was used to sample 30 students and 18 teachers. It was established that the students and teachers were computer literate and were able to manage computer applications for teaching and learning. The Learning process was found to be practical with learner interactions and activities based learning. The motivation was desire to teach better coupled with visionary, supportive school leadership. The school was using ICT as teaching learning tool and there was improvement of learning environment and outcomes. Many schools ought to emulate the school.

Inclusive education in an international school: A case study from Hong Kong - Chan, T.; Yuen, Mantak (International Journal of Special Education, 2015)
This case study provides an overview of current policy, practices and problems concerning inclusion in one international secondary school in Hong Kong. A total of 13 interviews were conducted with the school management team, teachers, students and parents, supplemented by 12 classroom observations and two ‘student-shadowing’ exercises. Findings suggest that the school has been reasonably successful in raising teachers’ awareness of inclusive education principles, creating a whole-school culture of inclusiveness, and forming a partnership with parents. However, the commitment of individual teachers to implementation of inclusive practices in their own classrooms varies. Some teachers are not adaptive enough in their teaching approach, and have difficulties differentiating instruction and learning activities. Improvements are also needed in the way that teachers work with their education assistants (classroom aides). Implications for improvement are discussed. © 2015, International Journal of Special Education. All rights reserved.

Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
Keywords: C: Ghana

Using Bronfenbrenner’s ecological theory to understand community partnerships: A historical case study of one urban high school - Leonard, Jack (Urban Education, 2011)

An Investigation on Learning Performance among Disabled People Using Educational Multimedia Software: A Case Study for Deaf People - Masitry, Ananthi Krishnasami; Majid, Mazlina Abdul; Toh, M Zulfahmi; Herawan, Tutut (2013)
The increasing number of people with hearing-impaired in Malaysia attracts to produce a variety of technologies, which can assist the deaf people in carrying out their tasks in everyday life as normal people. New technology can help to decrease the difficulty that hearing-impaired people faces in daily life to use the information services like normal people. Thus, this paper focuses on: i) developing a new multimedia courseware for pre-school students with hearing problem, and ii) comparing the deaf student’s learning performance before and after using the courseware. Four modules were developed for e-MSL courseware consist of alphabets, numbers, words and quizzes with colorful text, animation, sounds, video and pictures using Malaysian Sign Language (MSL). Sekolah Rendah Pendidikan Khas (SRPK) Indera Mahkota II, Kuantan has been chosen as the case study for data collection and for investigating the student learning performance on the courseware. The survey results show that 100% of the respondents have agreed that using e-MSL courseware managed to reduce the student learning time more than 80%. The result has indicated that students have shown better learning performance using e-MSL compared to traditional learning.

An investigation on learning Performance among disabled people using educational multimedia software: A case study for deaf people - Masitry, Ananthi Krishnasami; Majid, Mazlina Abdul; Toh, M. Zulfahmi; Sutarman, Sutarman; Herawan, Tutut (International Journal of Bio-Science and Bio-Technology, 2013)
The increasing number of people with hearing-impaired in Malaysia attracts to produce a variety of technologies, which can assist the deaf people in carrying out their tasks in everyday life as normal people. New technology can help to decrease the difficulty that hearing-impaired people faces in daily life to use the information services like normal people. Thus, this paper focuses on: i) developing a new multimedia courseware for pre-school students with hearing problem, and ii) comparing the deaf student’s learning performance before and after using the courseware. Four modules were developed for e-MSL courseware consist of alphabets, numbers, words and quizzes with colorful text, animation, sounds, video and pictures using Malaysian Sign Language (MSL). Sekolah Rendah Pendidikan Khas (SRPK) Indera Mahkota II, Kuantan has been chosen as the case study for data collection and for investigating the student learning performance on the courseware. The survey results show that 100% of the respondents have agreed that using e-MSL courseware managed to reduce the student learning time more than 80%. The result has indicated that students have shown better learning performance using e-MSL compared to traditional learning.
Keywords: ⛔ No INSPIRE recid found

Design and development of a Web Based Learning System in lower primary schools: A Case study of Makini Primary School, Kenya - Akinyi, Beatrice Ochieng (Moi University, 2015)
Web design technology arises from continued technological trend of computing. Globally the rise of application of information communication technology to the learning programme of primary schools is not much emphasized on. There is empirical evidence to prove that information communication technology is highly beneficial wherever it is applied. The study aimed at designing and developing a web based system of learning that can enhance the academic and social growth of lower primary school pupils. The objectives of the study were: to examine the correlation between the increased use of web based systems of learning and learner‟s academic performance; to identify the set of skills required for lower primary pupils to fully exploit the potential of web based systems of learning; to find out the specification and technical attributes of web based systems of learning that facilitate learning and lastly to design a web based learning system for lower primary school pupils. The study focused on Makini lower primary school in Nairobi County. The study employed case study method and qualitative approach. Rapid Application Development life cycle was used in software development process. Purposive sampling method was used to identify the respondents. Data was collected using interviews and focus group discussions. Findings of the study were: increased use of web based system that enhanced the learner‟s academic performance, the web based system of learning was able to identify games which exploit the pupils‟ skill in learning hence reducing monotony and lastly the web based system was able to identify some technical attributes such as use of graphics and access rights that facilitated learning and testing. The conclusion showed that developing of a web based learning system would reduce monotony in learning and enabled pupils to be in control and also increased the creativity and thinking level. The study recommends that: additions be made to the system such as a module to generate a feasible master timetable for each teacher; the web application of the system be further expanded to help attendance recording by the class teacher and for the parents to be able to view the status of their children performance using the Internet or Intranet of the school and lastly the system be made for every teacher to have some specific free periods or some part of days off and that will require an efficient search technique.
Keywords: ___working_potential_duplicate

Assessment of accelerated education to catch up with missed school programme in post crisis settings: Case study of selected IDP camps in Maiduguri metropolitan council - Wali, Yagana S; Muhammad Ali, Mustapha (British Journal of Educational Studies, 2019)
Keywords: ⛔ No DOI found

Education technology: An evidence-based review - Escueta, Maya; Quan, Vincent; Nickow, Andre Joshua; Oreopoulos, Philip (National Bureau of Economic Research, 2017)
In recent years, there has been widespread excitement around the potential for technology to transform learning. As investments in education technology continue to grow, students, parents, and teachers face a seemingly endless array of education technologies from which to choose—from digital personalized learning platforms to educational games to online courses. Amidst the excitement, it is important to step back and understand how technology can help—or in some cases hinder—how students learn. This review paper synthesizes and discusses experimental evidence on the effectiveness of technology-based approaches in education and outlines areas for future inquiry. In particular, we examine RCTs across the following categories of education technology: (1) access to technology, (2) computer-assisted learning, (3) technology-enabled behavioral interventions in education, and (4) online learning. While this review focuses on literature from developed countries, it also draws upon extensive research from developing countries. We hope this literature review will advance the knowledge base of how technology can be used to support education, outline key areas for new experimental research, and help drive improvements to the policies, programs, and structures that contribute to successful teaching and learning.
Keywords: ___working_potential_duplicate

E-learning tools for public awareness programme education in disaster risk management: Case study of the city of Cape Town disaster risk management centre - Kabaka, Martha; Stoltenkamp, Juliet (Proceedings of the International Conference on e-Learning, ICEL, 2013)
Disaster occurrence around the world has in the past few decades increased at an alarming rate necessitating an urgent need for mitigation strategies. As a result, research has indicated the usefulness of Information Communication Technology (ICT) in disaster risk management. Furthermore, ICT generally plays a critical role in all aspects of disaster risk management such as: early warning prediction; informing and circulating information relating to disasters to communities especially those at risk as promptly as possible and providing communication structures immediately after a disaster occurrence. As part of its planning and precautionary measures in responding to disasters, the City of Cape Town Disaster Risk Management Centre (CoCTDRMC) implements public awareness programmes across the city. The most acclaimed is an annual awareness programme especially for high school learners selected from various schools across the city. The learner participants are expected to act as change agents in their communities. In 2012, learners from twelve different schools across the city benefited from this programme. They were expected to educate families, friends, schoolmates and communities generally on the topical issues surrounding disaster risk management. This study uses a case study approach. Since the target audience of the programme is the youth, there is need to shift towards utilising ICT. The aim of this paper is to look at how e-learning as an ICT tool can be integrated in the implementation of Public Awareness Education Programme (PAEP), so as to target broader audience and create an increased capacity building across the City of Cape Town (CoCT). The examination considers providing tools that are accessible, dependable, resilient and flexible among the residents so as to reach the grassroots levels where communities are mostly affected. The paper considers a combination of tools so as to support behavioural change. Some of the research findings are that, the 2012 programme was very beneficial and successful. Henceforth there is need to target a broader audience, and although the CoCTDRMC does make use of some relevant ICTs, there is need for additional and upgraded technological resources. Also pertinent is the fact that e-learning can play a major role in making sure that a broader audience is reached if applied effectively. The findings of the research are of relevance to the CoCTDRMC and other municipalities across South Africa. The Centre for Innovative Educational and Communication Technologies (CIECT) at the University of the Western Cape can also use these findings to develop and implement an e-learning course for both employees of CoCTDRMC and other interested community members. This will guide them on how e-learning can assist in fostering a successful implementation of PAEP across the city.
Keywords: Disaster; Disaster risk management; E-learning; Information communication technology; Public awareness education programme; ⛔ No DOI found

Learning through Video Games: A Case Study of Private Schools of Pakistan - Khalid, Tooba; Batool, Syeda Hina (Ieee, 2018)
This study investigated video game based academic and information literacy (IL) learning of teenagers of private schools of Lahore city. Lahore is one of the big city and knowledge hub of Pakistan. Previous literature highlighted the importance of video games in learning academic and IL skills; therefore, the present study aims to reveal this fact in local context. The presented study adopted qualitative research approach and utilized phenomenological research method to achieve its objectives. The data was collected through interviews. The study participants were teenagers (13 to 19 years) of elite economic class private schools who were frequent video game players. Based on the study findings, it can be concluded that playing video games has positive impact on teenagers' learning. The majority of the participants were of view that challenges of completing various stages of games and interacting with online competitors enhanced their social (communication) and information literacy (searching/locating and evaluating) skills. The results of the study are benefitted for the game developers, teachers, librarians and parents.
Keywords: Pakistan; academic learning; information literacy; learning; skills; video games

Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers - Hanemann, Ulrike; Scarpino, Cassandra (UNESCO Institute for Lifelong Learning, 2016)
The UNESCO Institute for Lifelong Learning (UIL) has published a second edition of "Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers." This compilation of case studies from all world regions presents promising literacy and numeracy programmes that use information and communication technologies (ICTs) in their access and outreach strategies. The twenty-six case studies illustrate how ICTs such as radio, TV, mobile phones, tablets and computers can be used as media of instruction, can supplement face-to-face teaching, and can help to develop and strengthen youth and adult literacy, language and numeracy skills. The case studies featured in this publication can also be found in the UNESCO Effective Literacy and Numeracy Practices Database (LitBase). [For the 1st Edition: "Harnessing the Potential of ICTs for Literacy Teaching and Learning: Effective Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets, and Computers," see ED560504.]
Keywords: Adult Literacy; Case Studies; Distance Education; Educational Technology; Foreign Countries; Handheld Devices; Instructional Materials; Literacy Education; Mathematics Education; Numeracy; Program Content; Program Effectiveness; Radio; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; Television; Videoconferencing

Factors affecting the E-learning acceptance: A case study from UAE - Salloum, Said A.; Al-Emran, Mostafa; Shaalan, Khaled; Tarhini, Ali (Education and Information Technologies, 2019)
The main objective of this article is to study the factors that affect university students’ acceptance of E-learning systems. To achieve this objective, we have proposed a new model that aims to investigate the impact of innovativeness, quality, trust, and knowledge sharing on E-learning acceptance. Data collection has taken place through an online questionnaire survey, which was carried out at The British University in Dubai (BUiD) and University of Fujairah (UOF) in the UAE. There were 251 students participated in this study. Data were analyzed using SmartPLS and SPSS. The Structural Equation Modelling (SEM) has been used to validate the proposed model. The outcomes revealed that knowledge sharing and quality in the universities have a positive influence on E-learning acceptance among the students. Innovativeness and trust were found not to significantly affect the E-learning system acceptance. By identifying the factors that influence the E-learning acceptance, it will be more useful to provide better services for E-learning. Other implications are also presented in the study.

Advancing women’s digital skills and economic empowerment through girls in tech Indonesia: A case study - Afiani, Isyfi (Salasika, 2018)
The advancing Information and Communication Technology (ICT) has massively supported the economy in the digital era as it disseminates, stores, brings added value and manages information to provide unlimited opportunities for economic development. However, ICT may contribute to discrimination and existing inequalities reinforcement so-called the digital divide. Since all aspects of human interaction with ICT are gendered, this study tackles the digital gender divide issue, that is, the gap between men and women regarding access to, content and use of ICT. Accordingly, in 2016, the gender gap of global internet users was 12% and it grows every year. In response to this condition, a global movement promoting women engagement in ICT has emerged. This study, therefore, depicts the role of Girls in Tech Indonesia community as a chapter of Global Girls in Tech movement in advancing women economic empowerment through ICT by implementing transformational leadership concepts and Longwe’s empowerment framework. In the core of qualitative studies, this study shows that Girls in Tech Indonesia’s leadership performance contributes positively to women empowerment.
Keywords: Empowerment; Girls in Tech; ICT; Leadership; ⛔ No INSPIRE recid found

Challenges and opportunities for e-learning in education: A case study - Kafyulilo, Ayoub C. (Handbook of Research on Educational Technology Integration and Active Learning, 2015)
This chapter presents a review of literature on the existing opportunities and challenges of adopting e-learning in education in Tanzania and the possible measures to overcome some challenges. The study also assessed the primary factors contributing to the slow and limited use and integration of tec...

Using Educational Games for Sign Language Learning - A SignWriting Learning Game: Case Study - Bouzid, Yosra; Khenissi, Mohamed Ali; Essalmi, Fathi; Jemni, Mohamed (Journal of Educational Technology & Society, 2016)
ABSTRACT Apart from being used as a means of entertainment, computer games have been adopted for a long time as a valuable tool for learning. Computer games can offer many learning benefits to students since they can consume their attention and increase their motivation and engagement which can then lead to stimulate learning. However, most of the research to date on educational computer games, in particular learning versions of existing computer games, focused only on learner with typical development. Rather less is known about designing educational games for learners with special needs. The current research presents the results of a pilot study. The principal aim of this pilot study is to examine the interest of learners with hearing impairments in using an educational game for learning the sign language notation system SignWriting. The results found indicated that, overall, the application is useful, enjoyable and easy to use: the game can stimulate the students' interest in learning such notations.
Keywords: ⛔ No DOI found

Scrutinizing practicum for a more powerful teacher education: a longitudinal study with pre-service teachers - Tülüce, Serdar Hande; Çeçen, Sevdeger (Educational Sciences: Theory and Practice, 2016)
This study aims to explore the role of school-based practicum in promoting pre-service English language teachers' professional development through the use of a longitudinal design in combination with qualitative methods. To achieve this aim, pre-service teachers were asked to successively reflect on video-recordings of their micro-lessons in their university-based methodology courses directly after delivering the micro-lessons and retrospectively after their practicum experience. The participants of this study were 13 pre-service English language teachers studying at a foundation university in Istanbul, Turkey. The same data collection methodology was adapted before and after the practicum to gain a deeper understanding of the learning stemming from school-based practicum. The data for the study came from pre- and post-self-evaluation reports as well as pre- and post-focus-group interviews that had been collected based on the pre-service teachers' video-recorded microteaching simulations. The findings indicate that pre-service teachers commented on the same pedagogical, psychological, and physical factors they had noticed regarding their micro-lesson before and after the practicum. However, some qualitative changes were detected in their views over time as they had become more learner-oriented and had developed a more reflective view of teaching following the practicum. These findings have implications for the impact of practicum for future teacher education programs.
Keywords: Attitude Change; Case Studies; ERIC, Current Index to Journals in Education (CIJE); English (Second Language); Focus Groups; Foreign Countries; Higher Education; Language Teachers; Learning Processes; Longitudinal Studies; Microteaching; Physical Characteristics; Postsecondary Education; Practicums; Preservice Teacher Education; Preservice Teachers; Pretests Posttests; Professional Development; Psychological Patterns; Qualitative Research; Reflective Teaching; Second Language Instruction; Self Concept; Self Evaluation (Individuals); Simulation; Student Teacher Attitudes; Teaching Methods; Transformative Learning; Turkey (Istanbul); Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096126; __finaldtb

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Online learning community: A case study of teacher professional development in Indonesia - Sari, Eunice (Intercultural Education, 2012)
This paper investigates the concept of online learning community (OLC) to address the issues of teacher professional development practice in twenty-first-century Indonesia. Teachers in Indonesia are trained in a 'conventional way', hence, not ready to prepare the younger generations for entrance into the twenty-first-century complex life and work environment. The pedagogical transformation of a teacher can be facilitated through teacher professional development. Recent studies show that OLC holds great promise in improving teachers' professional practice. This paper presents key results of the introduction and trialling of OLC with Indonesian teachers and teacher educators between 2009 and 2010 and aims to explore the feasibility of this model to support professional development of teachers in this era. The social learning interactions among community members were examined using Scardamalia's Twelve Socio-Cognitive Determinants of Knowledge Building and Hoftsede's Cultural Dimension Review for Indonesia.

Evaluation of the application of mobile phone technology in teaching and learning: A case study of Kamwenja Teacher' college, Nyeri County, Kenya. - Gitome, Mwangi Joseph (Mount Kenya University, 2015)
This research was designed to investigate the application of mobile phone technology in teaching and learning among tutors and students of Kamwenja Teachers College in Nyeri County in Kenya. The problem this study addressed was to establish whether mobile phones in the hands of students and tutors were beneficial for teaching and learning or if they impede learning process in Teacher Training Colleges in Kenya. The variables under consideration were: quality teaching and learning as dependent variable and owning mobile phones, awareness of educational potential of mobile phones, acceptance of mobile phones, and mobile phones influence as alternative learning and instructional methods as independent variables. The data was collected from 71 tutors and 498 students. The sample size was worked out at 20% to be 15 tutors and 100 second year teacher trainees in the college. Stratified random sampling was used to ensure the sample was a true representation of the whole population. Data was collected through questionnaires that were both quantitative and qualitative to ensure high quality of information for the study where 98.2% response rate was achieved. To ensure Validity and Reliability of Research Instruments a pre-test of the questionnaire was conducted on tutors and students of Kagumo Teachers College. A reliability coefficient of 0.7 was adopted for the items while an expert, the supervisor, guided in validity of the items. The study was guided by the activity theory also known as Cultural Historical Activity Theory. Primary data was analysed with the aid of Statistical Package for Social Sciences (SPSS version 20) software to generate descriptive statistics, correlation and multiple regression analysis. The findings of the study revealed that ownership of mobile phone had a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly and even when regressed together with other factors. Further, the study revealed that awareness of the educational potential of mobile phone technology, acceptance of mobile phone technology and mobile phone technology as an alternative learning and instructional methods were found to have a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly, however when all the factors were regressed together they were found to have a positive and but insignificant effect on application of mobile phone technology in teaching and learning. In order to enhance use of mobile phone technology in teaching and learning students and teachers should be encouraged to acquire mobile phones with internet connectivity features. The general usage of mobile phone in teachers training colleges was found to be very high. However the rate at which mobile phones are used for exchanging learning information is low. The researcher recommends that policies be put in place on use of mobile phone technology in teaching and learning and train tutors on how to teach differently using mobile phone technology. Future researchers should try to establish hindrances of application of mobile phone technology in teaching and learning.

Towards the development of mobile learning model for Tanzania secondary schools: Case study Kilimanjaro region - Chambo, F. F.; Laizer, L. S.; Nkansah-Gyekye, Y.; Ndume, V. (2013 Pan African International Conference on Information Science, Computing and Telecommunications (PACT), 2013)
This paper explores the factors that influence the implementation of m-learning and proposes a model for implementing m-learning in Tanzania. The study was conducted in ten secondary schools in the Kilimanjaro region in Tanzania. Purposive and convenience sampling techniques were used to determine students majoring in science subjects. Findings indicate that majority of students own mobile phones and have access to the Internet connectivity. However, m-learning platforms that are currently in place are not viable solution in all contexts and not necessarily the best solution. Therefore, the design of m-learning content should focus on learning profile and personal needs such as location and affordability. A framework that considers four factors: user satisfaction, pedagogy, technology, and economy of use are proposed for Tanzanian context. It is concluded that education stakeholders should consider the opportunities of technology in education in order to boost knowledge sharing among students.
Keywords: Computational modeling; Context modeling; Educational institutions; Internet; Internet connectivity; Interoperability; Kilimanjaro region; Learning Science; M-Learning; Materials; Mobile handsets; Secondary School; Tanzania secondary school; computer aided instruction; economy of use; education stakeholder; emerging technology; knowledge sharing; m-learning; mobile learning; mobile learning model; mobile phone; pedagogy; sampling methods; sampling technique; science subject; user satisfaction

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

“He is suitable for her, of course he is our relative”: a qualitative exploration of the drivers and implications of child marriage in Gezira State, Sudan - Dean, Laura; Obasi, Angela; Sony, Asma El; Fadul, Selma; Hassan, Hanaa El; Thomson, Rachael; Tolhurst, Rachel (BMJ Global Health, 2019)
Introduction Child marriage is a fundamental development challenge for women and girls, with significant negative health and social outcomes. Sudan has a high rate of child marriage, with 34% of women aged 20–24 married before their 18th birthday. Since limited preventive interventions exist, we aimed to inform the evidence base to strengthen strategic action, using mixed qualitative methods to enhance study credibility. This study is the first to conduct a rigorous qualitative examination of the drivers of child marriage from the perspective of key stakeholders involved in marriage decision making within Sudan, and makes a significant contribution towards global knowledge by developing an evidence-based conceptual framework. Methods Initially, we completed 14 focus group discussions separated by gender with mothers, fathers, and girls married as adolescents, and 23 key informant interviews. We then used a critical incident case study approach to explore 11 ‘cases’ of child marriage (46 interviews). Results Findings indicate that gendered social norms and values, underpinned by religious beliefs and educational accessibility, interconnect to shape marriage decisions. In this context, many child marriages are triggered by an intrakinship proposal and further enabled by the relative lack of autonomy and influence of girls and women in marriage decision-making processes. Discussion Interconnected drivers demand context-specific holistic and multisectoral approaches, which should include simultaneous strategies to expand access to education, health services and livelihood opportunities, and evoke legal change, and participatory social and attitudinal processes that include the engagement of religious leaders and men.
Keywords: child health; qualitative study

MOOCs for in-service teachers: the case of Uganda and lessons for Africa - Oyo, B.; Kalema, B.M.; Byabazaire, J. (Revista Española de Pedagogía, 2017)
In recent times, computers and internet have penetrated secondary schools in Africa but with greater attention to students’ computer literacy than teachers. At the same time, previous studies on digital literacy of teachers are unsustainable and mainly skewed on pre-service teachers than in-service teachers. These realities point to the need to investigate and implement effective and sustainable initiatives for improving digital literacy and online life-long learning for in-service teachers in Africa. This paper therefore presents a specialised MOOC platform known as TEP (Teachers’ E-learning Portal) for digital literacy and online life-long learning for in-service teachers in Uganda. TEP is built for environments with inadequate access to computers, internet and technical assistance. As such, TEP is accessible online or offline, managed by accredited local universities in collaboration with beneficiary secondary schools, and runs on existing resources in schools (technical personnel, computers and internet). Results from initial implementation of a computer literacy MOOC through TEP indicate that irrespective of age, when teachers are adequately supported internally by their schools and externally by a university, can improve their digital literacy and subsequently engage in online life-long learning. In addition, the results both in terms of high percentage of teacher participants’ completions (89%) and high volume of educational e-content generated, confirm TEP as an effective, attractive, and self-sustainable MOOC platform for in-service teachers’ in resource constraint environments. The paper finishes with an analysis of the relevance of TEP to Africa.
Keywords: _Source:Intuitive; _THEME: Education management; _THEME: Teacher Professional Development; __:import:03; __:match:final; __:matched; __:study_id:2426079; __finaldtb

MOOCs for in-service teachers: the case of Uganda and lessons for Africa - Oyo, B.; Kalema, B.M.; Byabazaire, J. (Revista Española de Pedagogía, 2017)
In recent times, computers and internet have penetrated secondary schools in Africa but with greater attention to students’ computer literacy than teachers. At the same time, previous studies on digital literacy of teachers are unsustainable and mainly skewed on pre-service teachers than in-service teachers. These realities point to the need to investigate and implement effective and sustainable initiatives for improving digital literacy and online life-long learning for in-service teachers in Africa. This paper therefore presents a specialised MOOC platform known as TEP (Teachers’ E-learning Portal) for digital literacy and online life-long learning for in-service teachers in Uganda. TEP is built for environments with inadequate access to computers, internet and technical assistance. As such, TEP is accessible online or offline, managed by accredited local universities in collaboration with beneficiary secondary schools, and runs on existing resources in schools (technical personnel, computers and internet). Results from initial implementation of a computer literacy MOOC through TEP indicate that irrespective of age, when teachers are adequately supported internally by their schools and externally by a university, can improve their digital literacy and subsequently engage in online life-long learning. In addition, the results both in terms of high percentage of teacher participants’ completions (89%) and high volume of educational e-content generated, confirm TEP as an effective, attractive, and self-sustainable MOOC platform for in-service teachers’ in resource constraint environments. The paper finishes with an analysis of the relevance of TEP to Africa.
Keywords: _Source:Intuitive; _THEME: Education management; _THEME: Teacher Professional Development; __:import:03; __:match:final; __:matched; __:study_id:2426079; __finaldtb

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

#CostingEquity: The case for disability-responsive education financing - Myers, Juliette; Pinnock, Helen; Baboo, Nafisa; Lewis, Ingrid (International Disability and Development Consortium, 2018)
The #CostingEquity research project investigated the benefits of financing disability-inclusive education, the current state of education financing with regard to inclusion, and what needs to change in order for education financing to effectively support the realisation of SDG 4. The #CostingEquity research report addresses three broad questions: • How do international donors and domestic governments currently fund disability-inclusive education? • What are the gaps and challenges in financing disability-inclusive education? • What needs to change to increase quality, equitable financing for learners with disabilities? The report aims to contribute to a better understanding of the issues related to equitable financing for education for learners with disabilities. It considers additional marginalising factors such as gender, socio-economic status, social circumstances and urban/rural location. It offers key arguments for civil society activists, donors and government advisors to make the case for building and strengthening inclusive education systems. Detailed case studies provide useful examples of financing gaps, challenges and promising practice from developing country contexts, major education donors, and new and emerging philanthropic donor foundations. The focus of case studies and examples is on low and lower-middle income countries and were chosen to reflect a broad range of regions and countries.The report concludes with a series of recommendations for domestic and external financing approaches.

Education for people and planet: creating sustainable futures for all - UNESCO (2016)
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Using online peer assessment in an instructional technology and material design course through social media - Demir, Mehmet (Higher Education: The International Journal of Higher Education Research, 2018)
This study was designed to investigate the student teachers perceptions about and benefits and challenges of using Facebook as an online peer assessment tool for the student teachers' works. The study group included 24 student teachers in science education department of a state university located in the southeast region of Turkey. A case study approach of the qualitative method was employed in the research. Semi-structured interviews were conducted to collect the data. The interviews were audio recorded, and records of all the interviews were transcribed into full text in Turkish. Collected data were analyzed using an emergent coding approach. Codes, then, were categorized to constitute themes and subthemes. The findings indicated that the student teachers were able to give objective feedback on their peers' work and engaged more actively in class after participating in online peer assessment. Additionally, the students found it exciting and productive to use Facebook as a peer assessment tool in their learning.
Keywords: Case Studies; Case studies; Coding; College students; Computer Uses in Education; ERIC, Current Index to Journals in Education (CIJE); Education--Higher Education; Educational Technology; Educational technology; Feedback; Feedback (Response); Foreign Countries; Higher Education; Higher education; Instructional Technology and Material Design; Internet; Interviews; Learner Engagement; Learning; Mass media; Peer Evaluation; Peer assessment; Peers; Preservice Teachers; Qualitative Research; Qualitative research; Science education; Semi Structured Interviews; Social Media; Social classes; Social media; Social networks; Structured interviews; Student Attitudes; Student teachers; Students; Teachers; Technology; Turkey; __:import:01; __:match:final; __:matched; __:study_id:2097831; __finaldtb

Digital Gender Divide or Technologically Empowered Women in Developing Countries? A Typical Case of Lies, Damned Lies, and Statistics - Hilbert, Martin (Social Science Research Network, 2011)
The discussion about women’s access to and use of digital Information and Communication Technologies (ICT) in developing countries has been inconclusive so far. Some claim that women are rather technophobic and that men are much better users of digital tools, while others argue that women enthusiastically embrace digital communication. This article puts this question to an empirical test. We analyze data sets from 12 Latin American and 13 African countries from 2005-08. This is believed to be the most extensive empirical study in this field so far. The results are surprisingly consistent and revealing: the reason why fewer women access and use ICT is a direct result of their unfavorable conditions with respect to employment, education and income. When controlling for these variables, women turn out to be more active users of digital tools than men. This turns the alleged digital gender divide into an opportunity: given women’s affinity for ICT, and given that digital technologies are tools that can improve living conditions, ICT represent a concrete and tangible opportunity to tackle longstanding challenges of gender inequalities in developing countries, including access to employment, income, education and health services.
Keywords: Damned Lies; Digital Gender Divide or Technologically Empowered Women in Developing Countries? A Typical Case of Lies; Martin Hilbert; SSRN; and Statistics

Networks and Power: Why Networks are Hierarchical Not Flat and What Can Be Done About It - Faul, Moira V. (Global Policy, 2016)
Many scholars, policy makers and practitioners associate new, networked forms of collaboration and governance with positive attributes such as speed, flexibility, adaptability and ‘flatness’. This article contrasts the assumptions that networks essentially moderate external asymmetries of power with the network theoretical view that networks may amplify existing hierarchies. The case study network explored supports the network theoretical view that existing power relations may be increased when a multistakeholder partnership network is established. The use of Social Network Analysis facilitates the comparison of the structures and relationships into which global policy actors are organised (the formal network) with the relationships and relational structures into which they choose to organise themselves (informal network). In the conclusions, I introduce the practice of network rewiring that could overcome the network mechanisms that amplify existing power relations. Further research is required that adds more case study evidence in order to raise (and begin to answer) questions that will give a wider view of the social structuring of power in partnership networks in international development, such as those referred to in the recently-adopted Sustainable Development Goals (SDGs).

Tusome Midline evaluation 2017 final report from DEC - Freudenberger, Elizabeth; Davis, Jeff (2017)
Keywords: ⚠️ Invalid DOI

The Primary Math and Reading Initiative (PRIMR) - RTI International (2014)

An Investigation into Implementation of ICT in ECD and Primary Schools, in the Light of Free Laptops at Primary One: a case study of teachers implementing ICT into their teaching practice - Tonui, Betty C.; Kerich, E.; Koross, R.; J, K.; Moi, Too (2018)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley

Mathematical modelling in teacher education: dealing with institutional constraints - Barquero, Berta; Bosch, Marianna; Romo, Avenilde (ZDM: The International Journal on Mathematics Education, 2018)
Considering the general problem of integrating mathematical modelling into current educational systems, this paper focuses on the "ecological dimension" of this problem--the institutional constraints that hinder the development of mathematical modelling as a normalised teaching activity--and the inevitable step of the professional development of teachers. Within the framework of the Anthropological Theory of the Didactic, this step is approached using the "study and research paths for teacher education" (SRP-TE), an inquiry-based process combining practical and theoretical questioning of school mathematical activities. We present a research study focusing on the design and analysis of an online and distance-learning course for in-service mathematics teachers based on the SRP-TE methodology. This course starts from the initial question of how to analyse, adapt and integrate a learning process related to mathematical modelling and how to sustain its long-term development. Our analysis is based on a case study consisting in four successive editions of a course for Latin American in-service mathematics teachers held at the Centre for Applied Research in Advanced Science and Technology in Mexico. The starting point is a modelling activity about forecasting the number of Facebook users, which includes functional modelling and regression. The results show how the course represents a valuable instrument to help teachers progress in the critical issue of identifying institutional constraints--most of them beyond the scope of action of teachers and students and not approached by previous research--hindering the integration of mathematical modelling in current secondary schools.
Keywords: Anthropological theory of the didactic; Barriers; Case Studies; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Ecological Factors; Ecology; Foreign Countries; Functions; Inservice Teacher Education; Institutional constraints; Instructional Design; Mathematical Models; Mathematical modelling; Mathematics Teachers; Mexico; Online Courses; Prediction; Regression (Statistics); Social Media; Study and research path; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095891; __finaldtb

An Investigation into Implementation of ICT in Primary Schools, in Kenya, in the Light of Free Laptops at Primary One A Case Study of Teachers Implementing ICT into Their Teaching Practice - Tonui, Betty; Kerich, E; Koross, R (Journal of Education and Practice, 2016)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley region of Kenya. It examines views in pertinent literature as well as teachers’ perceptions of the benefits of integrating ICT into teaching-learning, the success factors and obstacles encountered in their endeavours to do this. Conclusions are drawn and suggestions made to address the challenges and improve on the use of ICT for teaching-learning in teaching institutions.
Keywords: ⛔ No DOI found

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

Empowered educators: how high-performing systems shape teaching quality around the world - Darling-Hammond, Linda (Jossey-Bass, 2017)
Keywords: Case studies; Education and state; Teachers; Training of

Behavioral Insights for Public Policy: Concepts and Cases - Ruggeri, Kai; Jarke, Hannes; Berkessel, Jana; Benzerga, Amel; Hlavova, Renata; Immonen, Johanna; Kunz, Marvin; Ojinaga Alfageme, Olatz; Paul, Alessandro; Plohl, Nejc; Prinz, Gerhard; Steinnes, Kamilla; et al. (2019)
https://www.routledge.com/Behavioral-Insights-for-Public-Policy-Concepts-and-Cases/Ruggeri/p/book/9781138484238 The first decades of the 21st century have offered a remarkable shift in how policies are made as well as who designs them. Until this period, advisory boards for local, regional, and national policy strategies largely comprised economists, lawyers, and financial experts. These panels made recommendations based on standing theory and, in some cases, subject-matter expertise, such as energy or healthcare. What has changed is how the behavioral sciences, largely psychology, have been embraced within these groups, thanks largely to extensive evidence from empirical research in how populations save, spend, eat, exercise, and work. While the application to policy may have contemporary versions, the behavioral side of economic theory itself is not new. Relevant insights on this go at least as far back as the 18th century with Daniel Bernoulli and Adam Smith, and continued steadily over the next two centuries with significant works from the likes of Wilhelm Wundt, Herbert Simon, and Roald Coase, among many others. However, how it came to be is perhaps more critical than merely who drove it. In each of these waves, a major shift in thinking was often preceded by empirical study that either attempted to explain how humans apply logic, or by surprising deviations from what appears to be rational. This textbook covers a range of topics from the origins of policy through to how recent advances in theory and practice have shifted our thinking on outcomes for society. Each section, including the fundamentals of behavioral sciences, policy development and evaluation, and all of the domains – economic, health, energy, education, workplace – cover examples of how behavioral insights are being used to address some of the most critical challenges we face. The cases and concepts presented in this book demonstrate the considerable value, both realized and potential, in studying as well as implementing behavioral insights into a variety of policy domains. We are still very much in the early days of this field, which means that these are merely fundamentals for educating and inspiring future generations of researchers, policymakers, and government leaders. As progress continues, how ultimate goals relevant to society are defined and targeted will become an increasingly important refrain amongst those involved in developing them. In these ways, we can consistently align our approaches with the most critical matters of local, national, and global communities: our safety, our stability, and our well-being.

Review of international research on factors underlying teacher absenteeism - Lee, Mary; Goodman, Crystal; Dandapani, Nitara; Kekahio, Wendy (Regional Educational Laboratory Pacific, 2015)
Throughout the U.S.-affiliated Pacific Region, teacher absenteeism has posed a long-standing challenge. This report draws on research literature from international contexts and case studies to identify the underlying factors that may relate to teacher absenteeism. Resources included in this report were selected with a focus on non-U.S. Pacific entities and emerging economy contexts that might be most relevant to the U.S.-affiliated Pacific Islands. Different search parameters were used to determine the scope of U.S./international literature to include in the review. The report found five main themes to consider in relation to teacher absenteeism: pay structure (for example, direct or indirect working relationship with the school), management (for example, school governance), working conditions (for example, school culture or single- vs. multi-grade classroom structure), community conditions (for example, teachers' proximity to the school), and social and cultural responsibilities (for example, illness, funeral attendance, and care of family members). Predictors of absenteeism vary across place and context. Given the diversity of Pacific Region communities, stakeholders should examine the extent to which the context and results of the research in this review correspond to the social, structural, cultural, and environmental characteristics of their own contexts. The following are appended: (1) Data and methodology; and (2) Viewing absenteeism through an international lens. A list of selected literature on teacher absenteeism in the United States is also included.
Keywords: Academic Rank (Professional); Accountability; C:LMIC; Case Studies; Community Characteristics; Correlation; Cross Cultural Studies; Cultural Context; Cultural Influences; Elementary School Teachers; Family Work Relationship; Foreign Countries; LMICs; School Administration; School Culture; School Location; Social Influences; Teacher Attendance; Teacher Salaries; Teaching Conditions; Work Environment; ⛔ No DOI found

Review of International Research on Factors Underlying Teacher Absenteeism. - Lee, Mary; Goodman, Crystal; Dandapani, Nitara; Kekahio, Wendy (Regional Educational Laboratory Pacific, 2015)
Throughout the U.S.-affiliated Pacific Region, teacher absenteeism has posed a long-standing challenge. This report draws on research literature from international contexts and case studies to identify the underlying factors that may relate to teacher absenteeism. Resources included in this report were selected with a focus on non-U.S. Pacific entities and emerging economy contexts that might be most relevant to the U.S.-affiliated Pacific Islands. Different search parameters were used to determine the scope of U.S./international literature to include in the review. The report found five main themes to consider in relation to teacher absenteeism: pay structure (for example, direct or indirect working relationship with the school), management (for example, school governance), working conditions (for example, school culture or single- vs. multi-grade classroom structure), community conditions (for example, teachers' proximity to the school), and social and cultural responsibilities (for example, illness, funeral attendance, and care of family members). Predictors of absenteeism vary across place and context. Given the diversity of Pacific Region communities, stakeholders should examine the extent to which the context and results of the research in this review correspond to the social, structural, cultural, and environmental characteristics of their own contexts. The following are appended: (1) Data and methodology; and (2) Viewing absenteeism through an international lens. A list of selected literature on teacher absenteeism in the United States is also included.
Keywords: Academic Rank (Professional); Accountability; Case Studies; Community Characteristics; Correlation; Cross Cultural Studies; Cultural Context; Cultural Influences; Elementary School Teachers; Family Work Relationship; Foreign Countries; Institutional Characteristics; Predictor Variables; Proximity; Sanctions; School Administration; School Culture; School Location; Social Influences; Teacher Attendance; Teacher Salaries; Teaching Conditions; Work Environment

Digital Study Hall: Lighthouse Case Study - Dover, Mark (Global Solution Networks, 2013)

Case Study Report: RET International Kenya - Boisvert, Kayla (University of Massachusetts Amherst, 2017)

Digital mismatch: Expectations and realities of digital competency amongst pre-service education students - Duncan-Howell, Jennifer (Australasian Journal of Educational Technology, 2012)
Pre-service education students entering university can be categorised broadly into two distinct groups, those who are coming directly from secondary school and those who are not. The second group can be quite diverse, ranging in age, academic and/or work experience. However, what both of these groups share is a digital expectation and they expect upon completion of their studies to be more digitally fluent than when they entered university, they expect to be taught via a range of digital technologies and they expect to use their digital skills throughout their personal and professional lives. These expectations have been either largely ignored or have failed to be understood by universities, resulting in a mismatch between student expectations and their experiences. However, the teaching staff within universities may be ill-prepared to meet these demands, either due to being non-users or exhibiting the same or lower levels of digital fluency as their students. The mismatch between student expectations and the reality is highlighted by an empirical case study involving undergraduate students enrolled in pre-service education degrees at an Australian university. The study will present clear evidence that students' digital expectancy should be considered when planning and improving learning environments.

Blog-based professional development of English teachers in Mumbai: the potential of innovative practice under scrutiny - Khan, Atiya (Australasian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
Keywords: Action Research; Case Studies; Communities of Practice; Diaries; ERIC, Current Index to Journals in Education (CIJE); Electronic Publishing; English (Second Language); Faculty Development; Foreign Countries; India; Language Teachers; Participant Observation; Private Schools; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Semi Structured Interviews; Teacher Collaboration; Web Sites; Workshops; __:import:01; __:match:final; __:matched; __:study_id:2096053; __finaldtb

Tiblo: a tangible learning aid for children with dyslexia - Pandey, Sumit; Srivastava, Swati (Association for Computing Machinery, 2011)
Dyslexia is a learning disability, which affects the ability to read and spell correctly. Special schools for children with dyslexia focus on individual growth, learning and psychological difficulties faced by the child. In this paper, we describe the design, development and testing of Tiblo (Tangible Interactive BLOcks), a tangible learning aid for children with dyslexia in the age group of 8 to 12 years. Tiblo has been specifically designed keeping in mind the psychological and emotional effects of dyslexia. We explain the process and results of an ethnographic study conducted at a school for children with dyslexia; the resulting concept development and prototyping. Further, we outline the testing process with the students at the school and the results of the same. The results showed that the children have a greater engagement in their classroom activities and there is an improvement in their retention abilities on using Tiblo. Also, they had a very strong sense of attachment and ownership towards the blocks and like to personalize it. This was in sharp contrast with other digital learning aids which offer a symptomatic and subject specific approach to aiding children with dyslexia and hence do not develop a personal one to one relationship with the child.
Keywords: collaborative learning; design case study; dyslexia; emotional design; interaction design; learning aids; play and learn; tangible user interfaces

Making mobile learning work: case studies of practice - Traxler, J.; Wishart, J. (Discussions in education, 2011)

Realising Affordable Internet in Bangladesh: A Case Study - Shadrach, B. (Alliance for Affordable Internet A4AI, 2016)

Empowering student learning through Tablet PCs: A case study - Li, Sandy C; Pow, Jacky WC; Wong, Emily ML; Fung, Alex CW (Education and Information Technologies, 2010)

The iPad as a Tool For Education - a case study - Heinrich, P. (2012)

Investigations into using data to improve learning: Philippines case study - Read, Lindsay; Atinc, Tamar Manuelyan (Global Economy and Development at Brookings, 2017)

Digital literacy in Ugandan teacher education: Insights from a case study - Andema, Samuel; Kendrick, Maureen; Norton, Bonny (Reading & Writing-Journal of the Reading Association of South Africa, 2013)
Keywords: ⛔ No DOI found

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
Keywords: ___working_potential_duplicate

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
Keywords: ___working_potential_duplicate

Increasing Interactivity in Distance Educations: Case Studies Bangladesh and Sri Lanka - Andersson, Annika; Hatakka, Mathias (Information Technology for Development, 2010)

Synergies between the principles for digital development and four case studies - Haßler, Bjoern (REAL Centre, Faculty of Education, University of Cambridge, 2018)
Keywords: ___working_potential_duplicate

Do No Harm teaching case study: Cité Soleil. Reference for workshop participants - Robillard, Sabina Carlson (CDA Collaborative Learning Projects, 2015)
Keywords: ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)

Barriers to the Use of Computer Assistive Technology among Students with Visual Impairment in Ghana: The Case of Akropong School for the Blind - Ampratwum, Joseph; Offei, Yaw Nyadu; Ntoaduro, Afua (Journal of Education and Practice, 2016)
The study aimed at exploring barriers to the use of computer assistive technology among students with visual impairment at Akropong School for the Blind. A case study design was adopted and the purposive sampling technique used to select 35 participants for the study. The researchers gathered qualitative data using an in-depth interview guide to investigate barriers to the use of keyboarding skills and Job Access with Speech (JAWS).Data were transcribed and analysed thematically. That is the key themes were identified in the conversations and these were drawn and discussed. This was done using both the narrative methods and opened quotes from interviews. The findings indicated that challenges limiting effective use of computer assistive technology in the School were more personal than external influences. This was because most of the challenges were due to the individual response to the training and familiarity in developing their competencies in using computer assistive technology. Based on this, it was recommended that efforts should be made to stock the laboratory with additional computers. Directly in line with the first recommendation, it was further suggested that more practice time should be created for the students to maximize computer use. Also, Licensed JAWS must be acquired by the school to advance students’ competence in using computer assistive technology. A number of the challenges were expressed by the students on their non- familiarity with the JAWS. As a result, it was recommended that instructors and trainers at the school should engage the students in revised lessons on introduction to computer. This will help to refresh the minds of students.
Keywords: ⛔ No DOI found

Teachers’ perspectives on their use of ICT in teaching and learning: A case study - Kafyulilo, Ayoub; Keengwe, Jared (Education and Information Technologies, 2014)
This article presents the perspectives of science and mathematics teachers on their use of information and communication technology (ICT) in teaching and learning in Tanzania. The findings show that few teachers used computers for teaching and learning purposes while majority of them used computers for administrative purposes. Additionally, teachers were found to have limited confidence in using technology to facilitate specific concepts or skills, to support creativity, and to support students to learn complex concepts. Therefore, it is suggested that schools explore strategies ICT integration strategies that focus more on making a shift from teaching technology or using technology for administrative purpose to appropriate pedagogical uses that could enhance student learning.

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)

Teachers’ perspectives on their use of ICT in teaching and learning: A case study - Kafyulilo, Ayoub; Keengwe, Jared (Education and Information Technologies, 2014)
This article presents the perspectives of science and mathematics teachers on their use of information and communication technology (ICT) in teaching and learning in Tanzania. The findings show that few teachers used computers for teaching and learning purposes while majority of them used computers for administrative purposes. Additionally, teachers were found to have limited confidence in using technology to facilitate specific concepts or skills, to support creativity, and to support students to learn complex concepts. Therefore, it is suggested that schools explore strategies ICT integration strategies that focus more on making a shift from teaching technology or using technology for administrative purpose to appropriate pedagogical uses that could enhance student learning.

Slum dwellers' response to free primary education: a case study of Kibera slum, Nairobi - Njeru, Caroline N. (University of Nairobi, 2010)

Implementation of Information and Communication Technologies (ICTs) in Education Course: A Case from Teacher Education Institutions in Pakistan - Majoka, Muhammad Iqbal; Fazal, Shawana; Khan, Muhammad Saeed (Bulletin of Education and Research, 2013)
This research was aimed to explore the implementation of Information and Communication Technologies (ICTs) in education in teacher training programs in the Khyber Pakthunkhwa and Punjab provinces in Pakistan. It was the first time that the course "ICTs in Education" was implemented for ADE/B. Ed (Elementary) programs in session 2010-11. In this situation, it was vital to explore how successfully this course was implemented in the pioneer institutions, so as to have baseline information for further improvement in the implementation process. This study was focused to explore: (i) How the course "ICTs in Education" was implemented? (ii) How did the teacher educators follow the course guide and to what extent the course guide was helpful in implementing this course? Seven teacher training institutions (three from the Punjab and four from KP provinces) were selected as target population. The total sample was 40 teacher educators and 200 students from seven institutions. Mixed method research design was adopted to conduct this study. The data was drawn from the surveys for heads and prospective teachers, and semi-structured interviews with teacher educators. Analysis revealed that only in a few classrooms, different activities/ experiences as suggested in the unit were properly implemented, while in most that was not the case due to issues such as shortage of electric power supply, scarcity of ICTs tools and lack of training and skills in ICTs application. The extent to which teachers followed the course guide was another factor contributing to the implementation process.
Keywords: Barriers; Energy; Foreign Countries; Guides; Information Technology; Program Implementation; Teacher Education Programs; Teacher Educators; ⛔ No DOI found

Student acceptance of tablet devices in secondary education: A three-wave longitudinal cross-lagged case study - Courtois, Cédric; Montrieux, Hannelore; De Grove, Frederik; Raes, Annelies; De Marez, Lieven; Schellens, Tammy (Computers in Human Behavior, 2014)

iPad in education: A case study of iPad adoption and use in a primary school. - Henderson, S., & Yeow, J. (System Science (HICSS), 2012 45th Hawaii International Conference on, 2012)
Keywords: ⛔ No DOI found

Assessing the policy influence of research: A case study of governance research in Viet Nam - Pellini, Arnaldo; Anderson, James H; Tran, Huong Thi Lan; Irvine, Renwick (Overseas Development Institute, 2012)

Using Tactile Letters As An Assitive Techology in Teaching Alphabet For Dyslexi Children: A Case Study - Mohamad, Mariam; Tan, Abdullah; Sabrina, Jessica (eLearning & Software for Education, 2017)
Keywords: ⛔ No DOI found

A Social Informatics Analysis of Refugee Mobile Phone Use: A Case Study of Zaaatari Syrian Refugee Camp - Maitland, Carleen; Xu, Ying (SSRN Electronic Journal, 2015)

Check my school: A case study on citizen's monitoring of the education sector in the Philippines - Shkabatur, Jennifer (World Bank Group, 2012)

Effective Use of Assistive Technologies for Inclusive Education in Developing Countries: Issues and challenges from two case studies - Grönlund, Åke; Lim, Nena; Larsson, Hannu (International Journal of Education and Development using ICT, 2010)
Developing countries face many obstacles in the process of implementing inclusive education (IE). Effective use of assistive technologies (AT) can help governments in developing countries achieve inclusive education by helping children with disabilities in schools. Despite the importance and positive impact of AT, prior research on the use of AT in inclusive education especially in developing countries is limited. To fill the research gap in this area, this paper investigates the research question of, How can AT be effectively used for IE in developing countries? To address this question,...
Keywords: ⛔ No DOI found

Empowering Teachers to Promote Inclusive Education. A case study of approaches to training and support for inclusive teacher practice - Donnelly, Verity (European Agency for Special Needs and Inclusive Education, 2015)

A case study of the One Laptop per Child Project in Rwanda: Exploring the socio-cultural dimensions of delivery and implementation. - Girgis, R. (University of Cambridge, Cambridge, UK., 2015)

Leveraging Community and Government Resources for Gender and Educational Equity in India: A Case Study of Educate Girls | Educate a Child (educate a child, 2019)

Bridging between research and practice: Supporting professional development through collaborative studies of classroom teaching with technology - Hennessy, Sara (Sense Publishers, 2014)
This book presents a fresh approach to bridging the perceived gap between academic and classroom cultures. It describes a unique form of research partnership whereby Cambridge University academics and school teachers together grappled with and reformulated theory – through in-depth case studies analysing practice using interactive whiteboards in five subject areas. The inquiry exploited the collaborators’ complementary professional knowledge bases. Teachers’ voices are particularly audible in co-authored case study chapters. Outcomes included deeper insights into concepts of sociocultural learning theory and classroom dialogue, more analytical mindsets, sustained new practices and ways of working collegially. The book reflects upon the power of lesson video review and details how the co-inquirers negotiated “intermediate theory” – bridging educational theory and specific settings – framed in mutually accessible language and embodied in interactive multimedia resources for teacher development. These include video clips, analytic commentary from multiple perspectives, lesson materials, plus optional prompts for reflection and critique – not models of “best practice”. The resources make pedagogy explicit and vividly illustrate the book’s ideas, offering theory-informed yet practical tools designed with and for practitioners. Hennessy and colleagues have tested a model of ongoing, teacher-led development and innovation, professional dialogue and classroom trialing stimulated by discussing selected multimedia resources. The book will interest academic and teacher researchers, initial teacher educators, professional development leaders, mentors, plus practitioners interested in using interactive whiteboards and dialogic teaching. It explores widening approaches to collegial development to reach educators working in other contexts (with and without technology). This could involve intermediate theory building or shortcutting by sharing and adapting the outcomes – springboarding teachers’ further critique and professional learning. “I cannot recommend this book too highly … it weaves a complex developmental story with a range of facets. It emphasises clearly the rigour of the research that was conducted, while demonstrating the complexity of the inter-relationships, practices and issues for both teachers and researchers in developing practical and theoretical knowledge. Its graphic insights through text and associated media provide exemplars for teachers and those who work with teachers as a rich resource. It shows us all what can be achieved and the means of achieving it.” Prof. Barbara Jaworski, University of Loughborough

Fuzzy Boundaries Between Post-Disaster Phases: The Case of L’Aquila, Italy - Contreras, Diana (International Journal of Disaster Risk Science, 2016)
A number of indices have been developed for measuring vulnerability to disasters, but little attention has been paid to recovery indices. Post-disaster periods are usually divided into four phases. The terms established by the United Nations Development Programme for post-disaster phases—relief, early recovery, recovery, and development—are used in this article. This research examines the hypothesis that the boundaries between post-disaster recovery phases are fuzzy and should be defined by the progress achieved in the recovery process, rather than by the amount of time elapsed since the event. The methodology employed involved four steps: fieldwork, mapping, identification of indicators, and assessment. The case study area was the city of L’Aquila in the Abruzzo region of central Italy, which was struck by an earthquake in April 2009. For each phase of the recovery process in L’Aquila a score was calculated based on the progress observed in 2016, 7 years after the earthquake. The highest score went to the early recovery phase (14 points), followed by the recovery phase (13 points), the development phase (12 points), and the relief phase (4 points). The results demonstrate the possibility of defining post-disaster recovery phases in an affected area based on measuring achievements through indicators rather than defining recovery phases in terms of elapsed time after a disaster.
Keywords: Disaster recovery; Earthquakes; Geographical information system (GIS); L’Aquila; Post-disaster phases; Spatial indicators

Reciprocity among Farmers in Farming System Research: Application of Social Network Analysis - Jana, Rabindranath; Bandyopadhyay, Suraj; Choudhuri, Anil K. (Journal of Human Ecology, 2013)
In course of agricultural activities, farmers interact among themselves to fulfill different kinds of needs, such as getting advice regarding cultivation, obtaining appropriate seeds and plants, getting tools and implements, etc. On the basis of data to whom a farmer sends requests for such help and whether the farmer receives the required help, one can build a social network of help, whether simple or weighted, in agricultural production. The paper intends to study variation in measures of reciprocity among the farmers of the two villages in respect of different activities for agricultural production. For the study, two villages Madhya-Uttar and Astabari consisting of 88 and 79 households respectively were selected from unirrigated, rainfed area in the south-eastern region of the district of East Medinipur of West Bengal. To collect the required data, open-ended check lists were employed. A standardized graph theoretic measure (s3-measure) of reciprocity was applied to carry out social network analysis. In both the villages, values of reciprocity measures for seeds/plants and tools/implements exchange were more than that for advice giving; the measure for the network of agricultural activities as a whole was also greater than the network for social aspects. In case of all networks, values of s3-measure for the village Madhya-Uttar were much higher than Astabari. It indicates that the farming households of a network having greater value of s3-measure are more inter-dependent among themselves in agricultural production.
Keywords: In-degree; Out-degree; Reciprocal Pair; Simple and Weighted Social Networks; s3-measure

Online tools supporting the conduct and reporting of systematic reviews and systematic maps: a case study on CADIMA and review of existing tools - Kohl, Christian; McIntosh, Emma J.; Unger, Stefan; Haddaway, Neal R.; Kecke, Steffen; Schiemann, Joachim; Wilhelm, Ralf (Environmental Evidence, 2018)
Systematic reviews and systematic maps represent powerful tools to identify, collect, evaluate and summarise primary research pertinent to a specific research question or topic in a highly standardised and reproducible manner. Even though they are seen as the “gold standard” when synthesising primary research, systematic reviews and maps are typically resource-intensive and complex activities. Thus, managing the conduct and reporting of such reviews can become a time consuming and challenging task. This paper introduces the open access online tool CADIMA, which was developed through a collaboration between the Julius Kühn-Institut and the Collaboration for Environmental Evidence, in order to increase the efficiency of the evidence synthesis process and facilitate reporting of all activities to maximise methodological rigour. Furthermore, we analyse how CADIMA compares with other available tools by providing a comprehensive summary of existing software designed for the purposes of systematic review management. We show that CADIMA is the only available open access tool that is designed to: (1) assist throughout the systematic review/map process; (2) be suited to reviews broader than medical sciences; (3) allow for offline data extraction; and, (4) support working as a review team.
Keywords: Evidence synthesis; Managing systems; Rapid review; Review management; Systematic review software; Text mining; Time management; _Added-ailr-2024

Enhancing social inclusion through innovative mobile learning in Uruguay: case study by the UNESCO-Fazheng project on best practices in mobile learning - UNESCO Biblioteca Digital - UNESCO (2018)

Teachers’ conception towards the use of social networks as a tool for professional development in Tanzania government secondary schools: the case of Dodoma municipality - Manyama, Charles (University of Dodoma, 2017)
The current study sought to assess teachers' conception toward the use of social networks as a tool for professional development in Tanzania government secondary schools the case of Dodoma Municipality. Thus, the specific objectives of this study were to assess the influence of demographic characteristics on the use of social networks or as a tool for professional development. To assess teachers conception on the available social networks opportunity that can support professional development, to investigate teachers use of social networks available for professional development, to explore the perceived benefits of using social networks opportunity as a tool for professional development and to examine limitation that hinder teachers for professional development. The study was guided by social-cognitive theory, community of practice model (CoP) and technology acceptance model (TAM). A cross-section research design was used to collect data that involved 84 teachers‟ from ten secondary schools, six head of schools three quality assurers and one respondent from DEO office. SPSS computer program was used to analyze the data. Qualitative data were analyzes through content analysis and quantitative data were analyzed statistically using descriptive and inferential statistics by using SPSS Version 20, and Microsoft Excel were highly used. Linear regression techniques were used to seek whether there is a relationship between demographic characteristics and the use of social networks. The survey results showed that there is no significant relationship between demographic factors with the use of social networks as a tool for professional development. Either teachers have positive conceptions towards the use of social networks as a tool for professional development. Furthermore, teachers use SNs for communicating with their fellow from different groups but it is not effectively integrated into professional development. The findings indicate that, to a large extent, teachers agreed that SNs make them to be more creative and help them to improve their communication skills. In addition the findings indicated that teachers lack training on how to integrate SNs in TPD. Finally,the researcher recommend that, educational stakeholders should provide financial and material support to teachers in order to overcome challenge that limit the use of technology in teaching and learning.
Keywords: ⛔ No DOI found

The political economy of bad data: Evidence from African survey and administrative statistics - Sandefur, Justin; Glassman, Amanda (The Journal of Development Studies, 2015)
Across multiple African countries, discrepancies between administrative data and independent household surveys suggest official statistics systematically exaggerate development progress. We provide evidence for two distinct explanations of these discrepancies. First, governments misreport to foreign donors, as in the case of a results-based aid programme rewarding reported vaccination rates. Second, national governments are themselves misled by frontline service providers, as in the case of primary education, where official enrolment numbers diverged from survey estimates after funding shifted from user fees to per pupil government grants. Both syndromes highlight the need for incentive compatibility between data systems and funding rules.

Education, poverty and "purity" in the context of adolescent girls' secondary school retention and dropout: A qualitative study from Karnataka, southern India - Ramanaik, Satyanarayana; Collumbien, Martine; Prakash, Ravi; Howard-Merrill, Lottie; Thalinja, Raghavendra; Javalkar, Prakash; Murthy, Srikanta; Cislaghi, Ben; Beattie, Tara; Isac, Shajy; Moses, Stephen; Heise, Lori; et al. (PLoS ONE, 2018)
Background Gender-related norms and poverty remain important structural barriers to secondary school attendance among adolescent girls in southern India. We analyse how gender norms interact with family deprivation and dynamics to result in girls dropping out of school; we identify the main facilitators of school retention and changes to gender socialisation. Methods Longitudinal qualitative case studies with 36 girls were nested within a cluster randomized trial to evaluate the Samata intervention targeting adolescent girls in Bagalkote and Vijayapura districts in northern Karnataka. We used two rounds of in-depth interviews, conducted in 2014 at a time when respondents were in 8th standard at the age of 13 to 14 and sixteen months later. We combined thematic and narrative analyses. Results Our study found that poverty and socioeconomic realities at the household level strongly affect conformity with discriminatory gender practices such as restricting girls’ mobility. The value placed on education by parents clearly differentiates the regular school goers from those frequently absent and others who dropped out. With active encouragement of the girls’ educational and career aspirations, parents engendered the girl’s agency to communicate openly both at home and at school, allowing subtle changes to gender performance while resisting the pressure of social sanctions. In contrast, where educational aspirations were weak, parents invested more intensely in enforcing correct performance of gender, prioritising her well-being by aiming to secure her future in a good marriage. Among poorer families, girls’ domestic duties came at the cost of schooling with concerns about protecting her sexual purity predominating. Conclusions In contexts where a strong gender ideology of virginity before marriage rules, subtle shifts in harmful gender practices are possible. Interventions aiming to improve education need to target the most deprived families, focussing on trust building through open communication.

Early Childhood Longitudinal Study, Kindergarten Class of 1998–99 (ECLS) correct theta scores for the kindergarten through eighth grade data collections errata - Chapman, Chris (National Center for Education Statistics, 2010)
Find information about and locate all publications and data products on education information from the National Center for Education Statistics--NCES--. In most cases you may also browse the content of publications or download data files.

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

Real girls, real lives, connected: A global study of girls’ access and usage of mobile, told through 3000 voices. - Vodafone Foundation (Vodafone Foundation, 2018)

Value chain, stakeholders analysis and technology: A holistic and integrated approach for determining the cumulative added value of education - Khudair, Saud Abdullah Ben; Abdalla, Abdalla Khidir (International Journal of Educational Administration and Policy Studies, 2016)
Keywords: ⚠️ Invalid DOI

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language -- Study & teaching -- Foreign speakers; Education--Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS -- Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon; Mwanda, Samwel; Midigo, Ronnie; Maundu, John (American Journal of Education and Information Technologies, 2017)
The purpose of this study was to find out the extent of integration of computer technology into teaching and learning Biology in secondary schools of Rachuonyo South Sub-County, Kenya. The target population consisted of students and biology teachers in the Sub-County. Data was collected by use of questionnaires and an observation check list. From the study, most schools had few computers; teachers had inadequate training on use of computer applications; most teachers did not use computer technology for personal growth and instructional purposes. Inadequate number of computers in the sampled schools was the major challenge facing the integration of computer technology into the instruction process. The study recommends increased accessibility of computers, adequate training on use of computer technology and development of a policy framework to guide on the path to effective computer integration into instruction process.
Keywords: ⚠️ Invalid DOI

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Keywords: ⛔ No DOI found

A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine (Distance Education, 2018)
The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.
Keywords: Re-entry; dropouts; open distance e-learning

Prospective teachers' teaching experience: teacher learning through the use of video - Osmanoglu, Aslihan (Educational Research, 2015)
Background: Future teachers need to observe, interpret and analyse teaching during the initial teacher education period. The use of videoed teaching and learning in teacher education promotes reflection, and analysing videos of teaching is helpful in learning effective classroom practices that prospective teachers mostly do not have the chance to observe during fieldwork experiences. The analysis of videos of teaching can be seen as a way to enhance the development of prospective teachers' professional vision, which, in turn, improves instruction. Purpose: The purpose of this study was to examine prospective teachers' reflections on video examples depicting their own teaching experiences. It aimed to create a professional development environment to facilitate the prospective teachers' reflection on their own videos and those of their peers to improve their professional vision. Sample: This study was conducted with over 200 (in 31 groups) third-year prospective mathematics teachers in a university in Western Turkey. The student teachers, receiving training to teach first- to fourth-grade elementary school pupils, were taking a teaching methods course. Design and methods: In the first week of the semester, the student teachers, working in groups, were assigned mathematics topics to teach the elementary school pupils. During the semester, each group prepared by trying out their activities in front of other student teachers in other groups. At the end of the semester, one student teacher from each group presented a short lesson related to their mathematical topic to the elementary school pupils. This lesson was videotaped, then later it was watched and discussed by the student teachers. Of the student teachers who undertook the teaching in the videos, 22 volunteers agreed to be interviewed. All groups of student teachers provided written reflections on their experience. Selected videos of the class discussions about the videos of teaching were also used for triangulation. The data were analysed to identify the issues the prospective teachers reflected upon. A content analysis technique was employed. Results: The data indicated that the prospective teachers were able to reflect on several issues related to effective teaching, connect their theoretical knowledge to their practice and consider issues related to pupil learning and difficulties. Conclusion: The findings suggested that the use of video, together with discussions between the student teachers, had the potential to create promising learning opportunities for prospective teachers.
Keywords: Case Method (Teaching Technique); Case Studies; Case-based pedagogy; Content Analysis; Data Analysis; Discussion (Teaching Technique); EDUCATION of student teachers; EFFECTIVE teaching; ELEMENTARY school teachers; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Electronic Learning; Elementary Education; Elementary School Teachers; Foreign Countries; Higher Education; Knowledge Base for Teaching; Learning Activities; Mathematics Teachers; Methods Courses; Microteaching; Outcomes of Education; PROFESSIONAL education; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Reflective Teaching; Student Teacher Attitudes; Student Teachers; TEACHER education; TEACHING methods; TRAINING of student teachers; Teacher Effectiveness; Teaching Experience; Theory Practice Relationship; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096187; __finaldtb; class discussions; prospective teacher education; reflection; video case study

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Assessment of the effectiveness of ICT on Teacher Trainees in Colleges of education. A Case of St. Monica's College of Education - Osei Frimpong, Kojo; Asare, Samuel; Caroline, Owusu-Mintah (Asian Journal of Computer Science and Information Technology, 2019)
The use of ICT in teacher training colleges has relatively improve teaching and learning. The effective use of various ICT tools such the computer, smart phones and PDAs has brought innovative ideas in teacher trainees. This study aimed at finding out the factors influencing the use of ICT tools in enhancing teaching and learning process in the various teacher training institutions in Ghana. A survey was used in order to investigate the study. It was revealed from the findings of the study that students and tutors in the various colleges of education have now accepted the use of ICT in teaching and learning process. However some students still see ICT as difficult due to various factors such as inadequate computers in the various colleges for practical tution and poor access to the internet for learning.
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school factors and system, and other external factors. This exploratory study was conducted within the framework of a teachers’ union to understand members’ preparedness to integrate ICT tools in their teaching practices. Findings indicate the need for in-service professional development activities in the use of ICT for teaching, in teaching in multicultural environments, and in classroom management. Equally important is the role of school management and administration in the adoption and integration of ICT tools in education. In addition, the research provided clear evidence that despite the huge investments into ICT infrastructure by government, inequalities in ICT competencies among teachers remain. The most important conclusion is that the investments being made are politically motivated and that teachers are being side-lined in the decision-making processes and preference given to political visions.
Keywords: ⛔ No DOI found

Determinants of Implementation of Public Sector Projects in Kenya: A Case of Laptop Project in Public Primary Schools in Kangundo Sub-County, Machakos County - Muinde, Samuel Mutisya; Mbataru, Patrick (2019)
In One-to-one laptop programs are becoming popular across the globe. However available evidence suggests that their implementations in schools are often faced with challenges. For example, even though the government of Kenya began supplying laptops to public primary schools in 2016; reports indicate that the gadgets have not fully been put into use in many schools. Most of the empirical studies done in this area have majorly focused on the level of success and factors influencing implementation of the project and not the extent to which specific variables determine implementation of the project, thus resulting to a research gap. In order to fill this gap, study focused on the determinants of implementation of the laptop project in public primary schools in Kangundo Sub-county. The study was guided by 4 research objectives: i.) To assess the extent to which teachers’ perception determine implementation of the laptop project; ii) To establish the extent to which teachers’ capacity in ICT determine implementation of the laptop project; iii) To establish the extent to which availability of facilities determine the implementation of the laptop project; and iv) To establish the extent to which availability of digital subject content determine implementation of the laptop project. The study was premised on three (3) theories; Technology Acceptance Model, Constructivist Learning Theory and Resource Based Theory. The study adopted descriptive survey design. It targeted all the public primary schools, all teachers in lower primary and all the Ministry of Education officials heading the four zones that constitute Kangundo Sub-county. The study targeted all the 74 public primary schools which have 222 lower primary teachers, 74 head teachers and 4 MOEST officials making a total target population of 300. It adopted stratified random sampling in stratifying the schools into four zones and randomly selected 22 schools. All 22 school heads and all 66 lower primary school teachers of the participating schools were purposively sampled. Additionally, the 4 MOEST officials heading the four zones were included, making a sample of 92 participants. Tools of data collection included questionnaires for teachers and school heads, an interview guide for MOEST officials and an observation checklist. The data analysis was conducted using SPSS. Content analysis was adopted in analyzing qualitative data whereas descriptive statistics such as frequencies and percentages were used in analyzing quantitative data. Tables and figures were used to present the study results. The inferential analysis conducted shows that there was a significant relationship between independent and dependent variables. Both teachers’ capacity on ICT and availability of facilities were found to have significant effect on implementation of the laptop project while teachers’ perception and availability of digital subject content were found to have insignificant effect on the project in public primary schools in Kangundo Sub-County.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

E-learning in secondary Schools in Kenya: A Case of the NEPAD E-schools - Ayere, Mildred; Odera, F; Agak, John (Educational Research and Reviews, 2010)
The New Partnership for Africa's Development (NEPAD) schools were set up as centres of excellence in Information and Communication Technology (ICT) integration, so that other schools could copy their model in e-learning. It was for this reason that they were provided with computers, e-materials, internet appliances and trained personnel. But to gauge their levels of success as e-learning centres there was need to compare them to other schools offering ICT education in Kenya. It was for this reason that this study compared the application of the e-learning in NEPAD and non-NEPAD schools in Kenya. Specifically, the study: Identified significant differences in levels of integration of ICT in curriculum subjects; surveyed the differences in use of e-materials in education research; examined availability of e-libraries; identified significant differences in academic performance of NEPAD and non-NEPAD schools attributed to e-learning. The study used a combination of an exploratory approach using descriptive survey and ex-post-facto design. It was carried out in six of the eight provinces in Kenya, where the NEPAD schools are located. It targeted 1600 form four students from 35 secondary schools involved in ICT education (NEPAD schools included). Saturated sampling was used for the six NEPAD schools while six non-NEPAD schools were selected through simple random sampling. The sample consisted of three officials from the ministry of education, twelve principals and twelve heads of ICT department (HODs), and 570 of the form four students. The main data collection instrument was the questionnaire; administered to the students, the principals, and the HODs. The interview schedule was administered to the ministry of education personnel while an observation checklist was used as a confirmatory tool. Analysis was done using both descriptive and inferential statistics. The study found that, there was a significant difference in the application of e-learning in NEPAD and non-NEPAD schools. Based on these findings, it was recommended that schools involved in ICT education should intensify teacher facilitation and support teacher roles that are required in e-learning Key words: E-Learning, ICT integration, ICT education, new partnership for Africa's development (NEPAD).
Keywords: ⛔ No DOI found

Factors That Influence Teachers' Pedagogical Use of ICT in Secondary Schools: A Case of Ghana - Buabeng-Andoh, Charles (Contemporary Educational Technology, 2019)
Technology is perceived as a vital driving force for contemporary education. The Government of Ghana acknowledges the relevance of Information and Communication Technology (ICT) in education, and it is financing ICT in secondary schools. However, most instructors are unwilling to integrate ICT into their teaching. Therefore, the purpose of this study was to investigate the factors that influence secondary school teachers' ICT usage in schools. The participants were 376 teachers randomly selected from 24 public and private schools. The data collected from the participants were analyzed by using descriptive statistics and analysis of variance. The results showed that teachers' use of ICT was still confined to basic and traditional activities such as search for information, class presentation etc. Internal and external factors were found to influence teachers' ICT usage. Also, female teachers reported that they use ICT more than male teachers. In general, this study has contributed to the literature regarding teachers' pedagogical use of ICT in secondary schools and also their gender differences in the use of ICT.
Keywords: Access to Computers; Competence; Computer Uses in Education; Foreign Countries; Gender Differences; Influence of Technology; Information Technology; Instructional Leadership; Pedagogical Content Knowledge; Private Schools; Public Schools; Rural Schools; Secondary School Teachers; Secondary Schools; Self Efficacy; Teacher Attitudes; Technological Literacy; Technology Integration; Training; Urban Schools; ⛔ No DOI found

Using School Performance Data to Drive School and Education District Office Accountability and Improvement: The Case of Ghana - Prew, Martin; Quaigrain, Kenneth (Educational Management Administration & Leadership, 2010)
Distance-education delivery through interactive television (ITV) is an effective means of providing instruction to learners. There are many advantages, such as the ability to provide immediate feedback and personal participation. To be effective, however, ITV requires structured planning and development, making the use of instructional design principles imperative. The following recommendations are made for training teachers about ITV: (1) provide an overview of the technology and how it works; (2) provide hands-on guided practice; (3) incorporate effective elements of instruction; (4) conduct periodic follow-up inservice training; (5) train with teachers who volunteer; (6) establish the amount of time needed to prepare and teach ITV courses; (7) provide experiences with other faculty members; (8) incorporate strategies for adding visual components to audio courses; and (9) use strategies that encourage group cohesion and student motivation. Teachers must adapt instruction to meet the varied needs of students, as both teachers and students adjust to the demands of the medium. (SLD)
Keywords: Delivery Systems; Distance Education; Educational Planning; Educational Technology; Educational Television; Feedback; Graduate Study; Higher Education; Information Transfer; Instructional Design; Instructional Effectiveness; Interactive Television; Student Motivation; Teacher Attitudes; Teacher Education; Teaching Methods; Technological Advancement; Telecourses; Training; search_string_27b

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

Designing OLPC learning environments: A case on 1:1 pedagogy in rural Tanzania - Pakarinen, S.; Apiola, M.; Moisseinen, N.; Tedre, M. (2013 Africon, 2013)
In the past two decades computers have become a standard educational tool in the industrialized countries. Recently, equipping each student with a personal device (one-to-one computing, OLPC) has been enthusiastically advocated for developing countries, too. However, despite a number of pioneering research studies, broader analyses of pedagogical, technical, and organizational aspects of one-to-one computing in developing countries are largely missing. In this participatory action research in a rural Tanzanian primary school, we identified a number of pedagogical elements that were beneficial for teaching and utilizing ICT in the classroom. We pinpointed exploratory and self-regulated learning, group problem solving, and constructive principles as facilitators of learning within the one-to-one computing paradigm in this context. Our results show that the introduction of children's computers also triggered a number of changes in dynamics both within the school but also outside the school.
Keywords: Context; Educational institutions; ICT utilization; Interviews; Materials; OLPC learning environment; Portable computers; Tanzania; computer aided instruction; constructive principles; educational institutions; educational tool; exploratory learning; group problem solving; information and communications technology; learning facilitators; one-to-one computing; organizational aspect; participatory action research; pedagogical aspect; pedagogical elements; pedagogy; rural primary school; self-regulated learning; teaching; technical aspect

Negotiating problems of practice in research–practice design partnerships - Penuel, William R.; Coburn, Cynthia E.; Gallagher, Daniel J. (Teachers College Record, 2013)
This chapter focuses on how researchers and practitioners negotiate the focus of their joint work within design-based implementation research (DBIR). Studying and facilitating successful negotiation of the problems that become the focus of work and the search for solutions is important for developing DBIR, because of its commitment to focusing on persistent problems of practice from multiple stakeholders’ perspectives. Case studies of two different research–practice partnerships provide a context for exploring two different perspectives on negotiation. In one case study, the notion of partnerships as forms of cultural exchange across institutional boundaries that differ with respect to goals, norms, and practices is used to analyze a design partnership focused on repurposing curriculum units in elementary science. In the second case study, the concept of framing as developed in social movement theory is used to illuminate issues of status and authority within a partnership between a district and researchers. The chapter concludes by describing the contributions of each perspective to an understanding of how teams jointly negotiate the focus of their work and by providing some recommendations for how teams can do so successfully.

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology, EdTech, low-income countries, literature review

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK’s Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.
Keywords: Research methodology; ___working_potential_duplicate; education systems; mixed-methods research

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Motivating students to offer their best: evidence based effective course design - Stearns, Susan A. (College Teaching, 2013)
Sometimes we question whether students are incapable or capable and/or willing or unwilling in regards to their academics. This study determined where students lie in regards to these concepts and showed one example of motivating students to do their best via course design, in this particular case by the use of a writing process model.
Keywords: course design; effective teaching; higher education; process writing; student motivation

Education and International Development: An Introduction - McCowan, Tristan; Unterhalter, Elaine (Bloomsbury Publishing, 2015)
'Honorable Mention' 2016 PROSE Award - Education PracticeEducation is fundamental to every aspect of development and there is widespread support across the world for policies that affirm that all children, regardless of their circumstances, have a right to quality schooling. Yet despite concerted efforts from national governments, multilateral organisations and NGOs over many decades we are still far from achieving education for all. In addition, while education can enhance human development, it is also associated with persistent inequalities. Education and International Development provides a comprehensive introduction to the field, giving an overview of the history, influential theories, important concepts and areas of achievement, and presenting a critical reflection on emerging trends in policy, practice and research. With chapters that review key challenges and inspiring initiatives in countries around the globe - focusing on critical issues such as language, conflict and teachers - this book serves both as a companion to graduate studies in international education and a concise reference book for practitioners and educators in the field.
Keywords: Education / Comparative; Education / Multicultural Education

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK’s Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.
Keywords: Research methodology; ___working_potential_duplicate; education systems; mixed-methods research

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction--CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics--Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

Pathways to Impact: Insights from Research Partnerships in Uganda and India - Hinton, Rachel; Bronwin, Rona; Savage, Laura (IDS Bulletin, 2019)
This article sets out a perspective from the United Kingdom’s Department for International Development (DFID) on the challenges of achieving research uptake. Two country case studies are presented from India and Uganda, which explore research projects under the Economic and Social Research Council ESRC-DFID-funded Raising Learning Outcomes programme. These case studies focus on relationships between the key stakeholders that enable policy debate relevant to the funded research. They are not a direct assessment of the impact that this research has had. Rather, this article explores the messy and iterative processes that DFID advisers are engaged in within the networks that they are embedded (and those that they are not), the way that they use partnerships to access evidence and promote it into policy debate, and the other drivers that matter. This article is important as a contribution to ongoing efforts to improve the quality and usage of education evidence in low-income contexts.
Keywords: Impact; Policy Engagement; Research Partnership; Research Uptake

Teachers’ Perception About Integration of ICT in Teaching and Learning of Kiswahili Language in Secondary Schools in Kenya. - Miima, Florence; Ondigi, Dr Samson; Mavisi, Rose (2013)
This article discusses the results of exploratory study of integration of ICT in teaching and learning of Kiswahili language in Kenyan secondary schools taking the case of Kakamega county in western part of Kenya. A survey design technique was adopted. Forty five teachers were selected to act as sample size for the study. Questionnaires and interview protocols were used to collect the data. The data collected was analyzed through descriptive statistical techniques. The results are summarized and presented through tables and graphs. The findings established that most Kiswahili teachers understand the benefit of integrating ICT in teaching and learning of Kiswahili language but they are not willing to adopt it due to various challenges. The paper examines how Kiswahili language teachers integrate ICT into everyday classroom practice, their perceptions, constrains, and their reservations. It also considers use of ICT along with the influences of established curriculum practice and policy upon Kiswahili language teacher’s willingness to develop new forms of activity and pedagogy. The case study provides some information on integration of ICT at all level of language teaching and learning in education.

A cognitive assessment tool designed for data collection in the field in low-and middle-income countries - Ford, Cassie B.; Kim, Ha Yeon; Brown, Lindsay; Aber, J. Lawrence; Sheridan, Margaret A. (Research in Comparative and International Education, 2019)
The Rapid Assessment of Cognitive and Emotional Regulation (RACER) is a tablet-based assessment tool for children that measures executive function (EF) skills. Instructions that are brief and visually presented; game-like tasks are designed to easily engage children regardless of literacy level and variable test administration settings. RACER measures inhibitory control and working memory. This study presents the theoretical rationale and empirical evidence for tablet-based assessments of EF, the process of administering the RACER assessments. The current sample consists of students in Lebanon (N=1900) and Niger (N=850). The results indicate that individual differences in EF can be assessed by the RACER tablet tasks. Specifically, we demonstrate that EF scores are associated in expected ways with age and that tasks function similarly to what has been observed in high-income countries. The feasibility and utility for researchers, practitioners, and clinicians, of this cognitive assessment tool is discussed.

Blended learning for academic resilience in times of disaster or crisis - Mackey, Julie; Gilmore, Fiona; Dabner, Nicki (Journal of Online Learning and Teaching, 2012)
Blended learning can provide academic resilience in times of natural disaster, civil emergency, and crisis. While blended pedagogies are widely used in tertiary settings, very little has been written about the role of blended learning in times of crisis, or the pedagogical challenges of rapid course redesign to mitigate disruptive circumstances. This case study describes the immediate post-earthquake challenges of redesigning courses using different blends of face-to-face and online activities to meet the needs of on-campus, regional campus, and distance pre-service teacher education students. The research question asked, "What can be learned from the experiences of academic staff directly involved in the adaptation and redesign of blended courses in a time of disaster?" This descriptive case study employed quick-response research strategies to gather time-sensitive data while it was fresh in the minds of the participants. This article discusses key findings and concludes with recommendations to assist program and course leaders to prepare in advance for resilient blended learning in times of natural disaster, crisis, and emergency.

Computer literacy and e-learning perception in Cameroon: the case of Yaounde Faculty of Medicine and Biomedical Sciences - Bediang, Georges; Stoll, Beat; Geissbuhler, Antoine; Klohn, Axel M; Stuckelberger, Astrid; Nko’o, Samuel; Chastonay, Philippe (BMC Medical Education, 2013)
Background: Health science education faces numerous challenges: assimilation of knowledge, management of increasing numbers of learners or changes in educational models and methodologies. With the emergence of e-learning, the use of information and communication technologies (ICT) and Internet to improve teaching and learning in health science training institutions has become a crucial issue for low and middle income countries, including sub-Saharan Africa. In this perspective, the Faculty of Medicine and Biomedical Sciences (FMBS) of Yaoundé has played a pioneering role in Cameroon in making significant efforts to improve students’ and lecturers’ access to computers and to Internet on its campus. The objective is to investigate how computer literacy and the perception towards e-learning and its potential could contribute to the learning and teaching process within the FMBS academic community. Method: A cross-sectional survey was carried out among students, residents and lecturers. The data was gathered through a written questionnaire distributed at FMBS campus and analysed with routine statistical software. Results: 307 participants answered the questionnaire: 218 students, 57 residents and 32 lecturers. Results show that most students, residents and lecturers have access to computers and Internet, although students’ access is mainly at home for computers and at cyber cafés for Internet. Most of the participants have a fairly good mastery of ICT. However, some basic rules of good practices concerning the use of ICT in the health domain were still not well known. Google is the most frequently used engine to retrieve health literature for all participants; only 7% of students and 16% of residents have heard about Medical Subject Headings (MeSH). The potential of e-learning in the improvement of teaching and learning still remains insufficiently exploited. About two thirds of the students are not familiar with the concept of e-leaning. 84% of students and 58% of residents had never had access to e-learning resources. However, most of the participants perceive the potential of e-learning for learning and teaching, and are in favour of its development at the FMBS. Conclusion: The strong interest revealed by the study participants to adopt and follow-up the development of elearning, opens new perspectives to a faculty like the FMBS, located in a country with limited resources. However, the success of its development will depend on different factors: the definition of an e-learning strategy, the implementation of concrete measures and the adoption of a more active and participative pedagogy.

What have we learned after ten years of systematic reviews in international development? - Waddington, Hugh; Masset, Edoardo; Jimenez, Emmanuel (Journal of Development Effectiveness, 2018)
The paper discusses the role of systematic evidence in helping make better decisions to reach global development targets. Coming at the end of the ﬁrst decade of serious funding and support for systematic evidence generation in development economics and development studies, the paper presents opportunities and challenges for the continued development of systematic review methodologies. It concludes by introducing the papers collected in the issue, which make and demonstrate the case for theory-based approaches to evidence synthesis.
Keywords: Reviewed

Using Dual Systems theory to conceptualise challenges to routine when transforming pedagogy with digital technologies - Blundell, Christopher; Lee, Kar-Tin; Nykvist, Shaun (Teachers and Teaching, 2019)
(2019). Using Dual Systems theory to conceptualise challenges to routine when transforming pedagogy with digital technologies. Teachers and Teaching: Vol. 25, No. 8, pp. 937-954.
Keywords: Barriers; Case Studies; Classroom Techniques; Correlation; Educational Change; Information Technology; Learning Theories; Student Behavior; Systems Approach; Teacher Attitudes; Teacher Role; Teacher Student Relationship; Teaching Methods; Technology Integration; ⛔ No DOI found

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Impact of Education on Labour Market Outcomes in Rural and Urban India - Pradhan, K. C.; Parida, P. C.; Sarangi, Tapas (Reflecting on India’s Development: Employment, Skill and Health, 2018)
This paper examines the returns to education with respect to three labour market outcomes namely wages, employment and occupation using the National Sample Survey Office (NSSO) 68th round (2011–12) data. Wage equation (without selection bias) results point to the fact that returns to education increase at an increasing rate as the level of education increases and the impact of education is found relatively higher in the case of urban than rural areas. In case of employment, the study finds that compared to illiterates, the chances of higher educated people going to agriculture sector is less. This is true even in the case of rural areas whereas the interactive variable (education with rural dummy) is found negatively associated with employment in agriculture sector. Occupation results suggest that there is a strong association between higher education (under graduate and graduate and above) with professional occupations and less with agriculture and fishery and unskilled occupations, suggesting the need for improving education and creating quality employment opportunities in the rural areas that may help in arresting the growing urban burden.
Keywords: Education; Employment; India; Occupation; Urban-rural gap; Wages

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: Bangladesh; Education--Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

Deliverology 101: A Field Guide For Educational Leaders - Barber, Michael; Moffit, Andy; Kihn, Paul (Corwin Press, 2011)
'Michael Barber's pioneering work as head of my Delivery Unit helped ensure real progress, not just with our education reforms, but with healthcare and policing too. It attracted worldwide attention. This guide distils the wisdom he gained at that time and has refined since. I strongly recommend it.' - Tony Blair, Former UK Prime Minister 1997-2007A step-by-step approach to delivering resultsMichael Barber, former chief advisor on delivery to British Prime Minister Tony Blair, and his colleagues Andy Moffit and Paul Kihn thoroughly describe Barber's proven reform delivery processes in this practical field guide. The timing is ideal, as Barack Obama's administration prioritizes education reform. Citing education reform case studies from more than 20 countries, the authors assert that most previous reforms were unsuccessful due to failed implementation. This book focuses on how to accomplish meaningful results, including:- Significant and ongoing education reform- Excellence and equity across public educationThe authors illustrate a field-tested program that ensures reform is achieved in the most profound sense, with students able to see, feel, and reap the benefits of a high-quality education. It is based not only on the experience of the Blair administration but also on case studies of successful implementation of reform in the U.S. and elsewhere.Listen as Barber describes the importance of the book:
Keywords: Education / Decision-Making & Problem Solving; Education / Leadership

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (International Institute of Social and Economic Sciences, 2019)
All universities in South Africa are encouraged to use a Learning Management System such as Blackboard to facilitate blended learning. Despite, the availability of Blackboard at one university of technology in the country, some lecturers and students prefer utilising WhatsApp for teaching and learning. The purpose of this study is to investigate students and lecturers’ perspectives about learning and teaching using WhatsApp at a university in South Africa. The study was done using a qualitative case study within an intepretivist paradigm. It was guided by Garrison, Anderson and Archer’s Community of Inquiry as a theoretical framework. Sixteen students and two lecturers who heavily use WhatsApp were purposively selected to participate in semi-structured interviews and focus group discussions. The study found that lecturers use WhatsApp not only for communication purposes, but to foster collaborative learning among students. Although students noted some limitations which they experience when using WhatsApp, they preferred the social media to blackboard. The study concludes that although WhatsApp is response to students’ needs, it does not adequately prepare students to graduate with digital literacy skills expected by the Department of Education in the country.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425972; __finaldtb

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (International Institute of Social and Economic Sciences, 2019)
All universities in South Africa are encouraged to use a Learning Management System such as Blackboard to facilitate blended learning. Despite, the availability of Blackboard at one university of technology in the country, some lecturers and students prefer utilising WhatsApp for teaching and learning. The purpose of this study is to investigate students and lecturers’ perspectives about learning and teaching using WhatsApp at a university in South Africa. The study was done using a qualitative case study within an intepretivist paradigm. It was guided by Garrison, Anderson and Archer’s Community of Inquiry as a theoretical framework. Sixteen students and two lecturers who heavily use WhatsApp were purposively selected to participate in semi-structured interviews and focus group discussions. The study found that lecturers use WhatsApp not only for communication purposes, but to foster collaborative learning among students. Although students noted some limitations which they experience when using WhatsApp, they preferred the social media to blackboard. The study concludes that although WhatsApp is response to students’ needs, it does not adequately prepare students to graduate with digital literacy skills expected by the Department of Education in the country.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425972; __finaldtb

IDENTIFICAÇÃO DO MODELO DE NEGÓCIO DE UMA START-UP/TIC: ESTUDO DE CASO NA EMPRESA GEEKIE - Lulia Filho, Herivelto; Turri, Silvia Novaes Zilber; Silva, Eduardo Corneto; Santos, Edna de Souza Machado (Investigação Científica nas Ciências Humanas e Sociais Aplicadas 3, 2019)
This study does not only understand the state of the art of the startups, but also understand how a small company of technology-based structure, shape its business model to grow and strengthen their business. For this this article has how objective of research, identify and describe the business model of a Startup/ICT Brazilian that work in the area of the education. It was used the concepts of case study, when analyzing the company Start-up/ICT Geekie, but will be used only secondary data, being this research a documentary research. The results show that the adaptive learning platform Start-up/ICT Geekie offers innovative service, personalizing and customizing education schools where works. The business model creates value for students, teachers and schools. Limitations of this article are in not obtaining primary data direct in the Geekie company and have only one company as study focus which limits the understanding of the business model of firms in the education sector.

Cultivating a personal learning network that leads to professional change - Stewart, Benjamin L. (Northcentral University, 2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about teaching and learning and the practicalities teachers face in the classroom. The purpose of this qualitative multiple case study was to describe how ideas, materials, and social interactions form a PLN through online, informal pedagogical dialogues among English language educators as it relates to professional learning. The five participants of this study were selected from a total of 10 based on their willingness to complete an informed consent form, complete an initial online survey, interact with other professionals publically online, and participate in a final interview. The online survey contained demographic information about each case and included both open and closed items; a content analysis was done on public interactions that tool place online; and a final in-depth interview used open questions to inquire about how respective PLNs changed over time. All data was coded, categorized, and placed into themes based on the ideational, material, and social aspects of each PLN. The findings show that professional knowledge, skills sets, and overall dispositions emerge in unique ways based on how ideas, technologies, and personal contacts interrelate with each other over time, and that an individual’s PLN provides unanticipated benefits when sharing publicly online.
Keywords: 0444:Foreign language education; 0449:Educational leadership; 0710:Educational technology; Actor-network theory; Complexity; Content analysis; Education; Educational leadership; Educational technology; English; Foreign Language; Learning; Personal learning network; Polls & surveys; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2096277; __finaldtb

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Paying Per Diems for ICT4D Project Participation: A Sustainability Challenge - Sanner, Terje Aksel; Sæbø, Johan Ivar (Information Technologies & International Development, 2014)
The article highlights the contradictory role per diem payments play in swiftly attracting local participation in ICT for Development (ICT4D) projects, while undermining long-term capacity building and sustainability with such efforts. We discuss sustainability challenges endemic to ICT4D projects in light of our case study findings from a mobile phone–based intervention in a public health management information system (HMIS) in Malawi. We explore these challenges at multiple levels of analysis by drawing on the neo-institutional notion of “institutional logics.” For practitioners and policy makers, the article offers suggestions on how to counter some of the pitfalls associated with the use of per diems to incentivize ICT4D project participants. The study contributes to the institutional logics perspective by exploring empirically the intricate interdependence between two mutually reinforcing, yet seemingly incongruent institutional logics of development project impact and aid entitlement.
Keywords: ⛔ No DOI found

Child labour and school dropout in least-developed countries: empirical evidence from Lao PDR - Xayavong, Thidavong; Pholphirul, Piriya (International Journal of Education Economics and Development, 2018)
Even though topics related to child labour and school dropout have been studied worldwide, little attention has focused in the least-developed countries. This paper examines the impact of child labour on school dropout by using national representative data surveyed in the Lao PDR, which serves as a case study of a least-developed country. Using an average wage of children by province as an instrumental variable, findings indicate that child labour, especially with regard to girls, has a strong impact on driving school dropout. Parental educational attainment, particularly mother's education, seems to show a significant effect on reducing the probability of dropping out. Our evidence supports the need to provide free education programs that have not yet been established in least-developed countries such as the Lao PDR. At the very least, given limited government budgets, support can be targeted to help vulnerable groups and poor families.
Keywords: Lao PDR; child labour; least-developed countries; school dropout; ⛔ No INSPIRE recid found

Private engagement in refugee education and the promise of digital humanitarianism - Menashy, Francine; Zakharia, Zeena (Oxford Review of Education, 2019)
This paper examines the prevalence of technological interventions in education in emergencies through a case study of private participation in Syrian refugee education in Jordan, Lebanon, and Turkey. This research is conceptually situated within critiques of ‘digital humanitarianism’, simultaneously interrogating the role of technology in humanitarian responses and the roles of private actors who promote this technology. Our study demonstrates that a pervasive optimism concerning education technology in emergencies accompanies a surge in private actor engagement in Syrian refugee education. Findings indicate that while access to technology in educational settings is important to the Syrian refugee populations, private actors’ disproportionate focus on technology is problematic, particularly when technological interventions are viewed as panaceas for refugee education; designed free from coordination; driven by proﬁt motivations; and developed in a manner decontextualised from the learning context. This study attends to the necessity of countering the overwhelming optimism about technology as a panacea for refugee education, which fails to problematise the implications of interventions developed in the Global North for a distant ‘other’ in the Global South.

Private engagement in refugee education and the promise of digital humanitarianism - Menashy, Francine; Zakharia, Zeena (Oxford Review of Education, 2019)
This paper examines the prevalence of technological interventions in education in emergencies through a case study of private participation in Syrian refugee education in Jordan, Lebanon, and Turkey. This research is conceptually situated within critiques of ‘digital humanitarianism’, simultaneously interrogating the role of technology in humanitarian responses and the roles of private actors who promote this technology. Our study demonstrates that a pervasive optimism concerning education technology in emergencies accompanies a surge in private actor engagement in Syrian refugee education. Findings indicate that while access to technology in educational settings is important to the Syrian refugee populations, private actors’ disproportionate focus on technology is problematic, particularly when technological interventions are viewed as panaceas for refugee education; designed free from coordination; driven by profit motivations; and developed in a manner decontextualised from the learning context. This study attends to the necessity of countering the overwhelming optimism about technology as a panacea for refugee education, which fails to problematise the implications of interventions developed in the Global North for a distant ‘other’ in the Global South.
Keywords: GENERAL - to be categorised; Google Scholar/ "education technology" refugees

Building an online community: student teachers' perceptions on the advantages of using social networking services in a teacher education program - Habibi, Akhmad; Mukinin, Amirul; Riyanto, Yatim; Prasohjo, Lantip Diat; Sulistiyo, Urip; Sofwan, Muhammad; Saudagar, Ferdiaz (Turkish Online Journal of Distance Education, 2018)
This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collecting data involving forty-two student teachers. We organized our analysis and discussion around their perceptions and the contexts in which the advantages they perceived emerge. The analyses of the texts revealed that two salient themes with their sub-themes related to the advantages of using Social Networking Services (SNS) in a teacher education program were social interaction (peer discussion and platform to interact with supervisors or lecturers) and learning motivation and experience supports (self-directed learning, promotes critical thinking, content engagement). Some pedagogical and social implications are also discussed.
Keywords: Case Studies; College Students; Computer Mediated Communication; Critical Thinking; Data Analysis; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Focus Groups; Foreign Countries; Group Discussion; Higher Education; Independent Study; Indonesia; Interpersonal Communication; Learner Engagement; Learning Motivation; Practicums; Preservice Teacher Education; Qualitative Research; Social Networks; Student Teacher Attitudes; Teacher Education Programs; __:import:01; __:match:final; __:matched; __:study_id:2097353; __finaldtb

Building an online community: student teachers' perceptions on the advantages of using social networking services in a teacher education program - Habibi, Akhmad; Mukinin, Amirul; Riyanto, Yatim; Prasohjo, Lantip Diat; Sulistiyo, Urip; Sofwan, Muhammad; Saudagar, Ferdiaz (Turkish Online Journal of Distance Education, 2018)
This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collecting data involving forty-two student teachers. We organized our analysis and discussion around their perceptions and the contexts in which the advantages they perceived emerge. The analyses of the texts revealed that two salient themes with their sub-themes related to the advantages of using Social Networking Services (SNS) in a teacher education program were social interaction (peer discussion and platform to interact with supervisors or lecturers) and learning motivation and experience supports (self-directed learning, promotes critical thinking, content engagement). Some pedagogical and social implications are also discussed.
Keywords: Case Studies; College Students; Computer Mediated Communication; Critical Thinking; Data Analysis; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Focus Groups; Foreign Countries; Group Discussion; Higher Education; Independent Study; Indonesia; Interpersonal Communication; Learner Engagement; Learning Motivation; Practicums; Preservice Teacher Education; Qualitative Research; Social Networks; Student Teacher Attitudes; Teacher Education Programs; __:import:01; __:match:final; __:matched; __:study_id:2097353; __finaldtb

Female teachers in Tanzania: An analysis of gender, poverty and constrained capabilities - Tao, Sharon (Gender and Education, 2019)
Tanzania has made great strides in improving access to education; however, concerns about the quality of this education persist due to reports of teacher absenteeism, distraction and lack of preparation. Given this situation, this study aimed to investigate teachers’ values and contexts to provide nuanced understandings of teacher practice and behaviour, particularly with regard to how gender intersects with these. Ethnographic case studies were conducted at three Tanzanian schools and findings demonstrated that although men and women experienced similar material conditions, there were marked differences between their opportunities and constraints, which female teachers could readily relate to instances of absenteeism and distraction. A feminist interpretation of the capability approach was used to reflect on female teachers’ capabilities, constraints and agency; and socialist feminist theory was used to further elaborate on why male and female teachers differ in their valued capabilities, their levels of constraint and their actions resulting from negotiating constraint.

Assessing user acceptance toward blog technology using the UTAUT model - Pardamean, Bens; Susanto, Mario (International Journal of Mathematics and Computers in Simulation, 2012)
Blogs are among the many commonly used technologies for education and learning. They are also both conversational technologies and constructivist learning tools. Their interactive, collaborative, user-friendly, and instant archival features have transformed blogs into effective tools for enhancing case-based teaching methods in the asynchronous nature of the online environment. This study investigated the student populace’s acceptance of the blog technology through the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. UTAUT integrates eight theories from social psychology and sociology in order to examine the effects of major factors on behavioral intention and actual use of blog to learn e-business course materials and topic discussions. The results showed that both social influence and performance expectancy had a significant relationship with behavioral intention, whereas effort expectancy did not. In this study, behavioral intention did not have a significant relationship with actual usage level of blogs as a learning tool.
Keywords: ⛔ No DOI found

Rethinking research partnerships: Evidence and the politics of participation in research partnerships for international development - Fransman, Jude; Newman, Kate (Journal of International Development, 2019)
This article responds to the drive for research partnerships between academics and practitioners, arguing that while potential benefits are clear, these are frequently not actualized resulting in partnerships that are ineffectual or worse, exacerbate damaging or inequitable assumptions and practices. In order to understand/improve partnerships, a systematic analysis of the interrelationship between what counts as evidence and dynamics of participation is proposed. Drawing on data from a seminar series and iterative analysis of seven case studies of partnerships between Higher Education Institutions and International Non-Governmental Organisations, the article concludes by suggesting substantial shifts in the theory and practice of partnerships. © 2019 The Authors Journal of International Development Published by John Wiley & Sons Ltd
Keywords: INGOs; evidence; higher education; knowledge and power; participation; research partnerships

Staying or leaving? Designing for persistence in an online educator training programme in Indonesia - Burns, Mary (Open Learning: The Journal of Open, Distance and e-Learning, 2013)
This case study discusses factors impacting the attrition and persistence rates of 60 Indonesian educators in an online programme in 2010. Course designers developed three variations of a web-based programme – a fully online, hybrid and web-facilitated model – and placed 20 learners, all with similar technology skills, in the three different models. The online cohort experienced a 31% attrition rate while 100% of learners in the hybrid and web-facilitated models completed the programme. Data collection revealed that the greatest factor impacting attrition or persistence was the absence or presence of face-to-face interaction with the instructor and colleagues. This paper outlines programme design elements that learners found most helpful in successfully completing the course.
Keywords: Indonesia; completion; online learning; persistence; readiness

Development and evaluation of Ning social network for teaching training online surveillance - Mohd Nawi, Mohd Aliff; Jamsari, Ezad Azraai; Sulaiman, Adibah; Hamzah, Mohd Isa (Turkish Online Journal of Distance Education, 2013)
Supervision of teaching practice is an important aspect of training teachers in improving their teaching skills. Barriers such as distance and time factor are the constraints faced by the lecturers at the National University of Malaysia to communicate with the teacher trainees under their supervision. Therefore, this study aims to develop and evaluate a social-networking site Ning's platform for the supervision of lecturers to teach on-line training. This study used the case design where a total of nine teacher trainees involved in this study. It found that overall, acceptance of the use of the social-networking site Ning mean score at the highest level of 3.91. In addition, all student teachers have positive attitudes towards the use of the social-networking site Ning social-networking site and agree a suitable approach to the supervision of one of the online teaching practices. While the "blog" is the most active facility used by student teachers in which they do self-reflection. In conclusion, the social-networking site Ning has the potential to assist lecturers to carry out supervision on-line teaching practice. (Contains 5 figures and 1 table.)
Keywords: Courseware; ERIC, Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Interviews; Malaysia; Observation; Online Courses; Social Networks; Student Teachers; Supervisory Methods; Teacher Education Programs; Teacher Supervision; Teaching Methods; Trainees; Web 2.0 Technologies; __:import:01; __:match:final; __:matched; __:study_id:2098097; __finaldtb; ⛔ No DOI found

Where is the “theory” within the field of educational technology research? - Hew, Khe Foon; Lan, Min; Tang, Ying; Jia, Chengyuan; Lo, Chung Kwan (British Journal of Educational Technology, 2019)
Critics often characterise the study of educational technology as under-theorised. To test this assertion and to determine the extent of this criticism, the present paper reports an in-depth analysis of the 503 most recent empirical articles published in three selected education-technology-related journals (Computers & Education; Learning, Media and Technology; and British Journal of Educational Technology). These journals were selected because they publish studies related to all education settings rather than focusing on only a certain segment such as higher education; they have broad geographical catchment; and they were the most highly ranked journals in terms of their 2017 journal citation impact factor. The present paper examines how explicitly existing theory was identified in previous research, how theories were applied and how often these theories were advanced in education technology research. In the majority of cases, explicit engagement with theory was absent. Many studies either were wholly bereft of theories or made vague use of theory. Where theory was explicit, the articles were more likely to use theory to conceptualise the research, to inform the data collection or analysis process and to discuss the results. Very few articles reported findings that help us to learn something new about a particular theory (ie, little evidence of theory advancement).

Planning and designing educational technology for low-income communities: A participatory and proactive approach - Ezumah, Bellarmine (Disruptive Technologies, Innovation and Global Redesign: Emerging Implications, 2012)
This chapter is an excerpt of a study that addressed the above concern using the One Laptop Per Child (OLPC) projects in Nigeria and Ghana as a case. It also situates the OLPC XO-laptop as a disruptive technology, because it aims at altering the existing pedagogy of the communities in which it was introduced through its constructivist approach. Moreover, as with most disruptive technologies, the XO laptop project is considered revolutionary, dramatically cheaper than regular laptops, convenient, and provides a different kind of learning content. As with the theme of this chapter, the XO laptop, although possessing disruptive technological qualities, was unable to achieve its goal due to lack of thorough planning and implementation of the adoption process. Results from the study informed the author to posit a model for technology adoption in low-income communities that is considered inclusive, participatory, and proactive, involving all stakeholders in setting up a policy. Such policy is expected to serve as benchmark for measuring the congruency of any proposed product whether disruptive or sustainable to the local need before its adoption.
Keywords: ___working_potential_duplicate

Planning and designing educational technology for low-income communities: A participatory and proactive approach - Ezumah, Bellarmine (Disruptive Technologies, Innovation and Global Redesign: Emerging Implications, 2012)
This chapter is an excerpt of a study that addressed the above concern using the One Laptop Per Child (OLPC) projects in Nigeria and Ghana as a case. It also situates the OLPC XO-laptop as a disruptive technology, because it aims at altering the existing pedagogy of the communities in which it was introduced through its constructivist approach. Moreover, as with most disruptive technologies, the XO laptop project is considered revolutionary, dramatically cheaper than regular laptops, convenient, and provides a different kind of learning content. As with the theme of this chapter, the XO laptop, although possessing disruptive technological qualities, was unable to achieve its goal due to lack of thorough planning and implementation of the adoption process. Results from the study informed the author to posit a model for technology adoption in low-income communities that is considered inclusive, participatory, and proactive, involving all stakeholders in setting up a policy. Such policy is expected to serve as benchmark for measuring the congruency of any proposed product whether disruptive or sustainable to the local need before its adoption.
Keywords: ___working_potential_duplicate

Insights on ESL student teachers reflecting collaboratively online - Suppiah, Shubashini; Wah, Lee Kean, (PhD); Swanto, Suyansah, (PhD); Lajium, Denis Andrew, (PhD) (The English Teacher, 2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
Keywords: Collaboration; Distance learning; English as a second language--ESL; Linguistics; Malaysia; Problem solving; Professional development; Reflective practice; Researchers; Social research; Student teachers; Teacher education; Teaching; Web 2.0; __:import:01; __:match:final; __:matched; __:study_id:2095770; __finaldtb; ⛔ No DOI found

Insights on ESL Student Teachers Reflecting Collaboratively Online Shubashini Suppiah Institute of Teacher Education Gaya Campus - Lee, S; Swanto, K; Lajium, S; Suppiah, D; Suppiah, Shubashini (2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.

Insights on ESL Student Teachers Reflecting Collaboratively Online Shubashini Suppiah Institute of Teacher Education Gaya Campus - Suppiah, Shubashini; Lee, S; Swanto, K; Lajium, S (2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Life planning by digital storytelling in a primary school in rural Tanzania - Duveskog, Marcus; Tedre, Matti; Sedano, Carolina Islas; Sutinen, Erkki (Educational Technology & Society, 2012)
Storytelling is one of the earliest forms of knowledge transfer, and parents often use it for teaching their children values and knowledge. Formal schooling, however, is less inclined to use storytelling as a vehicle for knowledge transfer, and even less as a vehicle for modern self-directed, student-centered, and constructionist pedagogy. Research literature reports experiences on student-centered storytelling in schools, but there is little information about such learning environments using modern information technology. Using a case study approach, we collected qualitative data from a workshop that tested a number of constructionist pedagogical approaches and one-to-one computing technology in a hypercontextualized storytelling workshop. In that workshop, which took place in a Tanzanian primary school, pupils used their XO-1 laptops as digital media tools for expressing their dreams and solutions to overcoming challenges in life. Results of this study suggest that digital storytelling offers additional advantages when compared to traditional storytelling. Designers need to follow six principles for a successful digital storytelling workshop: commitment, contextual grounding, previous exposure to the context, involvement of local experts, atmosphere of trust, and realistic flexible planning.
Keywords: ⛔ No DOI found

Blog-based professional development of English teachers in Mumbai: The potential of innovative practice under scrutiny | Australasian Journal of Educational Technology - Khan, Atiya (Australian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
Keywords: ___working_potential_duplicate

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

‘They are visually impaired, not blind … teach them!’: Grade R in-service teachers’ knowledge of teaching pre-reading skills to visually impaired learners - Kao, Matiekase A.; Mzimela, Patience J. (South African Journal of Childhood Education, 2019)
Background: Teaching reading skills is the cornerstone of all learning; therefore, teachers’ adherence to this mandate is important. However, it becomes complicated and challenging if the teacher has to teach pre-reading skills to Grade R learners with visual impairments. In light of this challenge, researchers have endeavoured to determine the Technological Pedagogical and Content Knowledge (TPACK) that teachers should possess for the effective teaching of reading in classrooms with visually impaired learners.Aim: This article explores a small sample of in-service teachers’ knowledge of using Braille to teach pre-reading skills to Grade R learners with visual impairments.Setting: The study was conducted in a School for the Blind in Maseru, Lesotho, where three Grade R in-service teachers teaching learners with visual impairments were purposively sampled.Methods: This study is underpinned by Koehler and Mishra’s theory of TPACK. An interpretivist, qualitative small-scale case study approach was employed, using semi-structured interviews and classroom observations. Document analysis was also used to corroborate findings.Results: Findings reveal that although some of the participants possess a high level of technological knowledge, they tend to teach Braille as a ‘stand-alone’ skill and fail to integrate it with the teaching of other pre-reading skills to Grade R learners.Conclusion: In-service teachers showed limited knowledge of some of the essential skills for teaching pre-reading skills to Grade R learners who are visually impaired. The study calls for supportive in-service teacher education programmes that equip Grade R teachers of learners with visual impairments with the necessary skills to teach pre-reading skills.
Keywords: Braille; Grade R Learners; Pedagogical Knowledge; Pre-Reading Skills; Technological Knowledge; Visual Impairment

Community outreach projects as a sustainable way of introducing information technology in developing countries - Zlotnikova, Irina; van der Weide, Theo (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2015)
The paper describes an approach to the sustainable introduction of IT in developing countries based on international collaboration between students taking the form of a knowledge bridge. The authors consider the challenges for introducing information technologies in developing countries; one of these is lack of reading materials ultimately leading to lack of reading skills in pupils and poor overall performance. A theoretical framework for the sustainable introduction of IT is proposed. It comprises the following components: (1) the model of a knowledge bridge, (2) the managerial model of the interactions between key stakeholders, and (3) the model of impact of a Community Outreach Project (COP) on target schools. The proposed models have been mapped to the widely adopted DPSIR framework used in sustainable development studies. As a case study, the authors discuss the E-readers Project run in two primary schools in Northern Tanzania. The paper also demonstrates how interaction and collaboration between Tanzanian and Dutch students was organized during preparatory stage and project implementation. The paper concludes with general recommendations on how to run a sustainable IT-based COP. These recommendations have been drawn from the analysis of the COP experience in the developing country, namely Tanzania.
Keywords: ⛔ No DOI found

Teaching Practices in the 21st Century in Kenya: A Qualitative Approach - Kaume-Mwinzi, Regina K. (International Journal of Educational Excellence, 2018)
Education is an engine for the growth and progress of any society and it is responsible for building human capital which sets technological and economic growth. In the pre-technology education context, the teacher controlled the instructional process, the content was delivered to the entire class and the teacher emphasized factual knowledge. However, the current global demands in education require the use of approaches that are learner-centered and embracing integration of ICT. The purpose of this study is to establish the pedagogy used in Kenya for the 21st century learner. The case study design was used to collect qualitative data from three teachers who were purposively sampled from three education sub-sectors in Kenya: primary, secondary and university. The interview was guided by three research questions: Which teaching practices are used in Kenya? Which are the ‘best’ teaching practices in Kenya in the 21st century? What are the barriers for the ‘best’ teaching practices in Kenya? The findings were that the teaching methods currently in use were mainly teacher-centered although the respondents revealed that the ‘best’ teaching practices for the 21st century learner were student-centered. However, the barriers were large classes, lack of resources and facilities among other factors. The study recommends realignment of education policies to give priority to build pedagogical capabilities of teachers, provide digital tools and other resources. This would enable the 21st century learners’ opportunity to unleash their potential.

eSkwela project - eSchool for out-of-school youths and adults, Philippines - Kamei, M (2010 International Conference on Technology for Education, 2010)
There are 774 million non-literates globally (UNESCO, 2009) and there is the acute problem of illiteracy grave in South Asian region. The paper discusses the implementation of eSkwela project as Alternative Learning System (ALS) in Philippines. The initiative responds directly to a national development priority to bring elearning opportunities and Information Communication Technology (ICT) for learning resources to mobile teachers / instructional managers and out-of-school learners in the Philippines. The paper assesses how the eSkwela project initiatives have provided opportunities for remote and elearning, blended learning and how Alternative Learning System (ALS) has been supported by innovative use of ICT for content development. It presents a macro view, case study of the strategic approach, design, challenges and successes faced by the eSkwela project which is still a work in progress. Rudiments in ICT for Education for citizens to attain the new-age literacy and lifelong learning opportunities are also evaluated.
Keywords: Aging; Alternative Learning System (ALS); Blended Learning; Collaboration; Communications technology; Computer science education; Educational institutions; Educational products; Electronic learning; Learning Management System (LMS); Learning systems; Space technology; Technology management; Virtual Learning Environment (VLE); ⛔ No INSPIRE recid found

Classroom ICT integration in Tanzania: Opportunities and challenges from the perspectives of TPACK and SAMR models - Kihoza, Patrick; Zlotnikova, Irina; Bada, Joseph; Kalegele, Khamisi (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2016)
With the education systems demand of contemporary technologies, teacher trainees should be imparted with competencies and skills to integrate information and communication technology (ICT) into their future teaching and learning practices. This study assessed classroom ICTs integration opportunities and the challenges in relation to Technological Pedagogical and Content Knowledge (TPACK) and SAMR (Substitute, Augmentation, Modification, and Redefinition) models. The case study involved tutors and teacher trainees (N=206) from teacher training colleges. Results indicated that, majority of respondents have low pedagogical ICT competencies. However, tutors exhibited good knowledge level in all TPACK and SAMR constructs that we assessed, teacher trainees’ revealed poor skills and inefficient support on the use of basic ICTs (hardware, software, and associated peripherals). The impacts of TPACK and SAMR models characteristics related to the technology use planning and redesign of learning tasks was evident. Most of the challenges identified were associated to the lack of infrastructures, readiness to change and lack of competencies on pedagogical ICTs applications. Among others, we recommend the government to work on a harmonized ICT in education integration framework; that consider the existing opportunities and challenges facing Tanzania teacher training systems. Further work should focus on carrying out an experimental research design to unlock the existing ICT use realities.
Keywords: ⛔ No DOI found

School-based professional development in one Lebanese school: how much is too much? - Nabhani, Mona; Bahous, Rima; Hamdan, Zeina (Professional Development in Education, 2012)
This case study examines the attitudes of the secondary and middle school teachers at one school in Lebanon regarding the effect of the school’s professional development (PD) programs on the quality of their teaching practices and motivation. It also examines teachers’ attitudes regarding PD as well as their recommendations to improve the quality of the PD program provided by their school. Questionnaires, focus group interviews and observations were conducted to collect and triangulate data results. Results show that teachers regard PD in their school as beneficial in general but able to be enhanced further. Although the attitude of novice teachers towards PD is more favorable than that of veteran teachers, findings show that the overall teachers’ attitude towards PD is a negative one. Modifications and suggestions to improve the quality of the PD activities are proposed by the teachers. The school offers a prosperous PD program, but its fruitfulness will remain limited unless an organizational structure is created.
Keywords: Lebanon; professional development; schools; ⛔ No DOI found

Multilingual language policy and mother tongue education in Timor-Leste: a multiscalar approach - Caffery, Jo; Coronado, Gabriela; Hodge, Bob (Language Policy, 2016)
This article looks at multilingual, mother-tongue-based language policies influenced by colonial and postcolonial histories and globalization processes. We use multiscalar analysis to show these policies as creative responses to problems affected by national and international forces. Our study focuses on Timor-Leste, specifically a pilot mother-tongue-based multilingual education program. We analyse the program’s practices and successful outcomes, in the adverse circumstances of this small, impoverished, recently independent nation, as it attempts to manage high levels of linguistic diversity (16 mother tongues and a five-language destination system) through multilingual education. We also identify tensions and problems that impinge on the outcomes for this ambitious program. Despite the obstacles, Timor-Leste’s multiscalar multilingual literacy policy is an important case that reinforces the significance of mother tongue education as a response to global complexity. The pilot program provides valuable lessons for many other parts of the world with similar problems, particularly for nations with comparable colonial histories.

Broadening borders to build better schools: virtual professional learning communities - Carpenter, Daniel; Munshower, Paul (The International Journal of Educational Management, 2019)
PurposeThe purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic.Design/methodology/approachA phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013; Stake, 2010). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013).FindingsTeacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice.Research limitations/implicationsThe research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year.Practical implicationsThe findings from this study have practical implications for rural teachers and school implementation of a professional learning community model.Originality/valueThe promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).
Keywords: Collaboration; Communities of Practice; Computer Mediated Communication; ERIC, Current Index to Journals in Education (CIJE); Education; Educational technology; Faculty Development; Learning; Meetings; Preferences; Professional development; Professional learning communities; Rural Schools; Rural schools; School districts; Teacher Attitudes; Teacher Collaboration; Teacher collaboration; Teachers; Teaching; Virtual professional learning communities; __:import:01; __:match:final; __:matched; __:study_id:2095794; __finaldtb

Roles and student identities in online large course forums: Implications for practice - Baxter, Jacqueline Aundree; Haycock, Jo (The International Review of Research in Open and Distributed Learning, 2014)
The use of large online discussion forums within online and distance learning continues to grow. Recent innovations in online learning such as the MOOC (massive open online course) and concomitant growth in the use of online media for the delivery of courses in traditional campus based universities provide both opportunity and challenge for online tutors and learners alike. The recognition of the role that online tutors and student identity plays in the field of retention and progression of distance learners is also well documented in the field of distance learning. Focusing on a course forum linked to a single Level 2 undergraduate module and open to over 1,000 students, this ideographic case study, set in a large distance learning university, uses qualitative methodology to examine the extent to which participation in a large forum can be considered within community of practice (COP) frameworks and contributes to feelings of efficacy, student identity, and motivation. The paper draws on current theory pertaining to online communities and examines this in relation to the extent to which the forum adds to feelings of academic and social integration. The study concludes that although the large forum environment facilitates a certain degree of academic integration and identity there is evidence that it also presents a number of barriers producing negative effects on student motivation and online identity.
Keywords: C: United Kingdom; e-learning; higher education; online forums; online identities; online learning

Usage level and Attitude of The Secondary Level Teachers' in Bangladesh Towards ICT at Personal and Professional Arena - Kashem, Abul; Haque, Ziaul (2014)
Integration of information and communications technologies (ICTs) in education sectors is one of the prime objectives of Bangladesh from the last decade. This study is conducted to assess the level of using ICT and acceptance of new technology by secondary level teachers in Bangladesh in their professional and personal arena. The study revealed that in Bangladesh most of the secondary level teachers use computer and internet for their personal purpose and use computers 35 times in a day. It revealed that secondary level teachers are interested to spend for ICT purpose. It also revealed that there is a difference in ICT usage between male and female teachers but no difference of the same among the different level of the teachers. It was found that there is no difference in case of perception about ICT between male and female teachers but perception among different level of teachers about ICT is different. Unavailability of high speed and wireless connections, lack of computer knowledge, high cost at start-up and unwillingness of aged teachers are found as hindrance for use of ICT in secondary level teaching arena. The success of information and communications technology (ICT) applications in teaching is profoundly dependent on the level of computer use by secondary level teachers. Majority of the Secondary level teacher were interested to accept the new technology for their professional capability enhancement and serve the nation. This questionnaire-based study assessed the level of computer and internet use by Secondary level teacher in Bangladesh is not satisfactory but perception of secondary level teacher for accepting new technology is positive both in their personal and professional arena.
Keywords: ⛔ No DOI found

The specific skills required of teachers who deliver K–12 distance education courses by synchronous videoconference: implications for training and professional development - Rehn, Nicki; Maor, Dorit; McConney, Andrew (Technology, Pedagogy and Education, 2018)
The purpose of this research is to identify the specific skills required of videoconference teachers who teach K–12 distance education courses. Many schools and educational districts worldwide are using videoconference technology to deliver courses to students as an economic solution when they cannot afford specialised teachers at remote locations. However, teachers are rarely trained to use this instructional technology and must therefore translate their experience in face-to-face and/or online teaching to this alternative medium. The collective case study used observations and interviews of eight teachers across five schools to identify the specific skills required to teach in a way that they perceived as successful in a videoconference class. It was found that teachers are largely under-prepared with strategies to project presence, develop relationships, foster interaction, manage the course and teach content across a distance when the screen is the main tool of connection. The authors offer a path to improvement that involves supporting teacher action research, creating communities of inquiry and developing teaching quality standards specific to videoconference.
Keywords: K–12; Videoconferencing; distance education; instructional technology; teacher roles

Teaching game and simulation based probability - Koparan, Timur (International Journal of Assessment Tools in Education, 2019)
Technology and games are the areas where learners are most interested in today's world. If these two can be brought together within the framework of learning objectives, they can be an advantage for teachers and students. This study aims to investigate the learning environment supported by game and simulation. The games were used to evaluate the basic probability knowledge of the prospective teachers, to demonstrate the role of problem solving in the formation of the mathematical knowledge, and to enable discussing mathematical ideas in a worksheet. Simulations were used for visualization and a large number of experiments. The sampling of the study, by which case study research is adopted, is comprised of 40 prospective teachers at a state university in Turkey. The data were collected by introducing nine open-ended questions by means of games, worksheets and simulation activities. The questions asked relevant to the games include making predictions about the fairness of the games, playing the games in small numbers and in big numbers and the observation of the scores, calculation of the winning probabilities of the gamers both experimentally and theoretically, and their comparisons. The process of finding out the probability information underlying the games by the prospective teachers was analyzed qualitatively by means of worksheets, simulations and in-class observation, and the ways of thinking, intuitions, estimations, strategies, and opinions about the learning situation of the participants were tried to be determined. The results obtained put forward that the learning situation that was set up simultaneously contributed to the knowledge of probability and probability teaching of the prospective teachers; and that the candidates' opinions about the learning situation are positive.
Keywords: Computer Simulation; ERIC, Current Index to Journals in Education (CIJE); Educational Environment; Foreign Countries; Higher Education; Instructional Effectiveness; Knowledge Level; Mathematics Skills; Postsecondary Education; Prediction; Preservice Teacher Education; Preservice Teachers; Probability; Problem Solving; Student Attitudes; Turkey; __:import:01; __:match:final; __:matched; __:study_id:2098269; __finaldtb

Applying the information search process model to analyze aspects in the design of serious games for children with hearing impairment - Cano, Sandra; Alghazzawi, Daniyal M.; Arteaga, Jaime Muñoz; Fardoun, Habib M.; Collazos, César A.; Amador, Viviana Bustos (Universal Access in the Information Society, 2018)
Deaf children traditionally face greater challenges and encounter difficulties particular to their abilities. The Information Search Process model (ISP) is oriented in the context of the present work as a process of searching for information about children with a hearing impairment in the area of literacy, applying the different stages of the ISP model to identify different aspects of hearing impairment. A case study was carried out at the USAER school in Aguascalientes, Mexico, a school that enables children with hearing impairments to be included in regular secondary schooling. The children here are aged 12–15 years and have literacy problems. Eight children from 7 to 11 years of age were also evaluated in the Institute for Deaf and Blind Children in Cali, Colombia. The ISP model can be deemed to have been useful for identifying the relevant needs to support both teachers and deaf children. A need was identified, to construct a game that integrates the activities undertaken following the FitzGerald keys and in turn allow them to assess learning through different activities that help increase the semantic repertoire.

Toward a Successful Plan for Educational Technology for Low-income Communities: A Formative Evaluation of One Laptop Per Child (OLPC) Projects in Nigeria and Ghana - Ezumah, Bellarmine Anthonia (Howard University, 2010)
Copious educational technology projects have been implemented in several low-income communities by multilateral institutions, individuals, and governmental agencies. Statistics show that the majority of these initiatives fail to accomplish their objectives, thereby wasting colossal amounts of money, talent, and resources. Scholars aver that poor planning and implementation are the major deterrents to a successful technology project (Flagg, 1990; Osin, 1998; Warschauer, 2006). Responding to this problem, the current work seeks to provide a model for an effective plan for introducing educational technology that will yield a better result for elementary education. Using as a case the One Laptop Per Child (OLPC), a computer program initiated by MIT professor Nicholas Negroponte to enhance education in low-income communities, this study specifically evaluates the planning and implementation strategies employed in the OLPC pilot projects in Abuja, Nigeria and Accra, Ghana. A participatory research approach was employed and qualitative data were collected in situ using in-depth interviews and questionnaires with parents, school leaders, students, public educational officials, community leaders, subject-matter experts, and OLPC personnel involved in the OLPC projects at LEA Galadima Primary School, Abuja, Nigeria and Kanda Primary School, Accra, Ghana. The project under study is a Western initiative; thus, the dominant paradigm of development communication theory and its alternative, the participatory action research, were employed as the theoretical framework. Results from the study allowed the researcher to posit a model toward a better plan for educational technology adoption in low-income communities. Some highlights include the need for every country to establish a standardized educational technology objective, ability to raise funds enough to keep it going, the need to incorporate local materials as major content, and acknowledging input of local experts, and the teachers' role in the entire process.
Keywords: Applied sciences; Communication and the arts; Constructivist pedagogy; Education; Educational technology; Formative evaluation; Ghana; Low-income; Nigeria; One Laptop Per Child; ___working_potential_duplicate

Decolonisation in Universities: The politics of knowledge - Jansen, Jonathan (Wits University Press, 2019)
Shortly after the giant bronze statue of Cecil John Rhodes came down at the University of Cape Town, student protestors called for the decolonisation of universities. It was a word hardly heard in South Africa’s struggle lexicon and many asked: What exactly is decolonisation? This book brings together some of the most innovative thinking on curriculum theory to address this important question. In the process, several critical questions are raised: Is decolonisation simply a slogan for addressing other pressing concerns on campuses and in society? What is the colonial legacy with respect to curricula and can it be undone? How is the project of curricula decolonisation similar to or different from the quest for post-colonial knowledge, indigenous knowledge or a critical theory of knowledge? What does decolonisation mean in a digital age where relationships between knowledge and power are shifting? Strong conceptual analyses are combined with case studies of attempts to ‘do decolonisation’ in settings as diverse as South Africa, Uganda, Tanzania and Mauritius. This comparative perspective enables reasonable judgments to be made about the prospects for institutional take-up within the curriculum of century-old universities. Decolonisation in Universities is essential reading for undergraduate teaching, postgraduate research and advanced scholarship in the field of curriculum studies.Shortly after the giant bronze statue of Cecil John Rhodes came down at the University of Cape Town, student protestors called for the decolonisation of universities. It was a word hardly heard in South Africa’s struggle lexicon and many asked: What exactly is decolonisation? This edited volume brings together the most innovative thinking on curriculum theory to address this important question. In the process, several critical questions are raised: Is decolonisation simply a slogan for addressing other pressing concerns on campuses and in society? What is the colonial legacy with respect to curriculum and can it be undone? How is the project of curriculum decolonisation similar to or different from the quest for postcolonial knowledge, indigenous knowledge or a critical theory of knowledge? What does decolonisation mean in a digital age where relationships between knowledge and power are shifting? The book combines strong conceptual analyses with novel case studies of attempts to ‘do decolonisation’ in settings as diverse as South Africa, Uganda, Tanzania and Mauritius. Such a comparative perspective enables reasonable judgements to be made about the prospects for institutional take-up within the curriculum of century-old universities.

Viewpoints to ICT practices and hindrances from in Tanzanian secondary schools and teacher training colleges: Focus on classroom teachers - Muhoza, O. U.; Tedre, M.; Aghaee, N.; Hansson, H. (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
On the policy level, Tanzania has strongly committed to Information and Communication Technology (ICT) supported education on all levels of education. National policy documents give ICT a high priority in development of the country's educational system. Curricula have been revamped to accommodate for increased role of ICT in the society and education. Also educational institutions have explicated high expectations of ICT in the process of "massification of education." Several research studies, however, have showed little change in the classrooms. Surveys and case studies have showed that on the way from policy documents to strategy level and implementation level, something gets missing. The lack of ICT in education is clear in primary and secondary school, which is unsurprising, given that majority of schools also lack electricity and basic facilities, including proper classrooms, tables, and books. This study sets out to investigate, using thematic interviews of secondary school teachers in Tanzania, what processes and support structures do teachers consider to be lacking in terms of ICT supported education. Informants from teacher training colleges were also involved in order to bring out viewpoints from teacher training. The results confirmed a large number of earlier results, divided to six categories: school policy, implementation and administration on the school level, access to ICT, leadership and management, school culture, and teacher training. A number of new factors were also pinpointed: teachers' lack of awareness of government policies and documentation on several levels, lack of pedagogical readiness for e-learning and blended learning, and cultural concerns. Concerning what should come first, there was a chicken-and-egg-problem: it makes little sense to invest in rapidly aging ICT infrastructure and facilities if there is no human capacity to make use of those investments, and it makes little sense to invest in human capacity if there is no technological infrastructure to put quickly aging technical know-how into immediate use.
Keywords: Classroom Activities; Computers; Culture; Educational Technology; Educational institutions; Government; ICT management; ICT supported education; Information and Communication Technology (ICT); Internet; Interviews; Tanzania; Tanzanian secondary schools; Teacher education; Teachers' expectations; Teachers' experiences; Training; blended learning; classroom teachers; computer aided instruction; cultural concerns; e-learning; educational courses; educational curricula; educational institutions; educational system development; government policies; information and communication technology; information technology; national policy documents; pedagogical readiness; teacher training; teacher training colleges

Thematic Analysis: Striving to Meet the Trustworthiness Criteria - Nowell, Lorelli S.; Norris, Jill M.; White, Deborah E.; Moules, Nancy J. (International Journal of Qualitative Methods, 2017)
As qualitative research becomes increasingly recognized and valued, it is imperative that it is conducted in a rigorous and methodical manner to yield meaningful and useful results. To be accepted as trustworthy, qualitative researchers must demonstrate that data analysis has been conducted in a precise, consistent, and exhaustive manner through recording, systematizing, and disclosing the methods of analysis with enough detail to enable the reader to determine whether the process is credible. Although there are numerous examples of how to conduct qualitative research, few sophisticated tools are available to researchers for conducting a rigorous and relevant thematic analysis. The purpose of this article is to guide researchers using thematic analysis as a research method. We offer personal insights and practical examples, while exploring issues of rigor and trustworthiness. The process of conducting a thematic analysis is illustrated through the presentation of an auditable decision trail, guiding interpreting and representing textual data. We detail our step-by-step approach to exploring the effectiveness of strategic clinical networks in Alberta, Canada, in our mixed methods case study. This article contributes a purposeful approach to thematic analysis in order to systematize and increase the traceability and verification of the analysis.

Leaving no-one behind: Improving climate change and entrepreneurship education in sub-Saharan Africa through E-learning and innovative governance systems - Chirambo, Dumisani (Climate Literacy and Innovations in Climate Change Education: Distance Learning for Sustainable Development, 2018)
Poverty and climate change vulnerability is increasing in Sub-Saharan Africa (SSA) because the region lacks education and skills development facilities, and sustainable governance systems. Arguably, mainstreaming climate literacy in secondary schools through Information and Communications Technology (ICT) modalities can promote sustainable development and climate change resilience by providing early opportunities for the youth to gain knowledge and awareness of the behavioral and cultural changes that may foster improved climate change resilience. Through an inductive analysis based on research articles, case studies, policy briefs, and academic literature reviews, this chapter sought to highlight emerging ICT learning contexts in SSA as a means to determine the extent to which ICT may be used to promote climate change and sustainable development education in secondary schools. The chapter showed that climate literacy at secondary schools was being constrained by a lack of climate change education material and content on existing ICT learning platforms; and a lack of innovative governance systems to support governments in delivering climate literacy content to secondary schools and the youth. Consequently, to “leave no-one behind” requires non-state actors to develop and utilise innovative governance systems and digital climate literacy material that can complement government efforts to mainstream climate literacy at secondary schools.

Snapshots of student-teachers' experiences of DVDs in a learner support programme in a developing ODL context - Kok, Illasha; Blignaut, A. Seugnet (Africa Education Review, 2014)
The School of Continuing Teacher Education (SCTE) in South Africa delivers an Advanced Certificate in Education (ACE) Learner Support Programme to Open Distance Learning (ODL) students in Namibia, a developing sub-Saharan African country. This paper examines the experiences of student-teachers using DVDs included in the tutorial package. Fifteen participants from rural and remote areas of Namibia took part in a semi-structured focus group and individual interviews. A first phase analysis identified a set of codes and categories that guided the researchers to two themes to using DVDs: frustration and attitude. Student-teachers' frustration and attitude towards DVDs are linked to sufficient appropriate information, also available as a paper-based tutorial package. Although electronic learning material can assist in achieving curriculum goals and enrich students' learning experiences, students' expectations are paramount in the design and development of instructional DVDs.
Keywords: Adult Education; Case Studies; College Students; Computer Uses in Education; Continuing Education; Developing Nations; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Electronic Learning; Focus Groups; Foreign Countries; Higher Education; Inservice Teacher Education; Namibia; Open Education; Postsecondary Education; Qualitative Research; Semi Structured Interviews; South Africa; Student Attitudes; Student Experience; Teachers; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096343; __finaldtb

Snapshots of student-teachers' experiences of DVDs in a learner support programme in a developing ODL context - Kok, Illasha; Blignaut, A. Seugnet (Africa Education Review, 2014)
The School of Continuing Teacher Education (SCTE) in South Africa delivers an Advanced Certificate in Education (ACE) Learner Support Programme to Open Distance Learning (ODL) students in Namibia, a developing sub-Saharan African country. This paper examines the experiences of student-teachers using DVDs included in the tutorial package. Fifteen participants from rural and remote areas of Namibia took part in a semi-structured focus group and individual interviews. A first phase analysis identified a set of codes and categories that guided the researchers to two themes to using DVDs: frustration and attitude. Student-teachers' frustration and attitude towards DVDs are linked to sufficient appropriate information, also available as a paper-based tutorial package. Although electronic learning material can assist in achieving curriculum goals and enrich students' learning experiences, students' expectations are paramount in the design and development of instructional DVDs.
Keywords: Adult Education; Case Studies; College Students; Computer Uses in Education; Continuing Education; Developing Nations; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Electronic Learning; Focus Groups; Foreign Countries; Higher Education; Inservice Teacher Education; Namibia; Open Education; Postsecondary Education; Qualitative Research; Semi Structured Interviews; South Africa; Student Attitudes; Student Experience; Teachers; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096343; __finaldtb

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Investigating Thai teachers attitudes toward students with autism - Little, Cathy; Vibulpatanavong, Kanokporn; Evans, David (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2014)
Greater numbers of students with Autism are being educated in mainstream settings, enrolled in regular classes, placed with ‘regular’ students, and with teachers who often have limited experience or knowledge about their specific disability. Teachers, with limited knowledge of disability, struggle to successfully include these students into their classes. However, a powerful predictor of successful inclusion of students with a disability into mainstream classrooms is the attitude of the general education teacher (Ainscow, 2007). A plethora of research abounds to empirically support what is known about quality teaching practice for students with Autism, yet this same research highlights teachers concerns of lack of knowledge, lack of support systems and overriding legislative policy as primary obstacles to the inclusion process. Research suggests that teachers of students with Autism have limited knowledge about the specific traits and idiosyncrasies that define these students learning styles and behaviours.This research investigated the attitudes of Thai teachers toward their students with Autism. Attitudes were defined by four constructs: attitude toward inclusion, teacher effectiveness, academic climate, and social inclusion. A key premise of this research was that positive teacher attitude was strongly related to more successful outcomes for students. This research utilised a mixed methods design over two phases, using both survey data and qualitative case studies. The following paper reports only on phase one of the research, the responses to the Teacher Attitudes Survey. Participants of the study were 404 teachers from seven schools in Bangkok. Results showed an ongoing need to assist teachers in building their confidence and knowledge in catering for students with Autism in the regular classroom. Teacher confidence (effectiveness) in meeting the education needs of students with Autism was reported as limited, yet teachers reported their understanding about the social inclusion of students with Autism in the regular school setting to be positive. Keywords : Attitudes, Autism, Education, Inclusion, Social Inclusio
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

“Thinking Outside the Camp”: Education Solutions for Syrian Refugees in Jordan - Baeyer, Sarah Lebaron Von (Ethnographic Praxis in Industry Conference Proceedings, 2017)
This paper presents a case study of a project on education solutions for Syrian refugees in Jordan conducted between 2015–2017. First, it describes how ReD's methodological approach provided a unique perspective to studies on refugees. By immersing a team in the day-to-day lives and settings that most Syrian refugees experience in Jordan—i.e., outside of camps and in people's actual homes—ReD led its client to “think outside the camp,” something that relief agencies and companies often fail to do due to the refugee camp model of humanitarian assistance that, ever since WWII, has dominated the approach to refugees. Second, as a result of its unique methodological approach, ReD uncovered important findings about social networks and technology use and access in Syrian refugees’ homes and communities that ultimately shaped the client's perspective on solution development. For example, ReD's team of ethnographers found that nearly all out-of-camp Syrian households had at least one Smartphone in their possession, if not two or more, and that digital devices served as important tools of communication and community-building among people displaced by conflict. Consequently, ReD advised its client to tap into these pre-existing social networks and mobile technologies in order to develop an education solution that best fit refugees’ “real-life” practices. Ultimately, both ReD's methods and its findings led to a significant impact in how the client strategized on and developed their education solution, and can serve as a broader model for how to approach building services and/or products for displaced populations with access to basic mobile technologies. “The Jordanian educational/policy response to refugees is broken and will not easily be fixed or tinkered with. Solutions must work around this system.” (Education expert and activist working with vulnerable youth and school dropouts in Jordan)
Keywords: Google Scholar/ refugee education technology; RER theme_durable solutions

Decentralisation policy and practice in Ghana: the promise and reality of community participation in education in rural communities - Essuman, Ato; Akyeampong, Kwame (Journal of Education Policy, 2011)
In 1987, the government of Ghana embarked on a process to decentralise education management to districts as part of wider social and democratic governance reforms. A central part of this reform was the prescription of active community participation in the affairs of schools within their locality. This paper explores the different meanings community participation had for school community stakeholders. It examines the multiple understandings of how community and school relations work and the factors which influence this relationship. Drawing on case study data, it argues that much of the theoretical and policy expectations on representation and participation in education by community members are only evident in form, but not as intended in practice. In poor rural contexts, it is often the local elite and relatively more educated members of the community, who become the new brokers of decision-making and, through their actions, close up the spaces for representation and participation by community members in the affairs of schools. Furthermore, the extent of community participation appears to be shaped by a ‘social contract’ based on the principle of reciprocity of roles between the community and schools, and that increasingly teachers feel accountable to the traditional hierarchical educational structure, and not to the community. The paper argues that the realisation of decentralisation policy in education has to contend with the realities of local politics of influence in the community, and tap into the positive side of this influence to improve education service delivery.
Keywords: Ghana; Parent Teacher Associations (PTA); School Management Committees (SMC); ___working_potential_duplicate; community participation; decentralisation policy

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, E.; Laurillard, D. (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Keywords: BLENDED learning; CO DESIGN MOOCS REFUGEES TEACHERS THEORY OF CHANGE; DIGITAL technology; Design; Digital technology; Education; Google Scholar/ "blended learning" refugee education; Lebanon; MASSIVE open online courses; MOOCs; Online instruction; PROFESSIONAL education; Professional development; RER theme_supporting educators; TEACHER development; __:import:01; __:match:final; __:matched; __:study_id:2095772; ___working_potential_duplicate; __finaldtb; co-design; refugees; teachers; theory of change

Higher education reforms: Latin America in comparative perspective - Bernasconi, Andrés; Celis, Sergio (Education Policy Analysis Archives, 2017)
This article introduces a special issue of EPAA/AAPE devoted to recent higher education reforms in Latin America. The last two decades have seen much policy development in higher education in the region, examined and discussed by scholars in each country, but dialog with the international literature on higher education reform, or an explicit comparative focus, have been mostly absent from these works. By way of presentation of the papers included in this issue, we first provide an overview of major policy changes in higher education in the Latin American region since the 1990s. We then turn to the six works in this special issue to describe the theories and methods supporting them. Next, we illustrate how general analytic categories can be derived from single or multi country case studies to illuminate themes capable of cutting across the particulars of national contexts, with their unique traditions, policy paths, and politics. Our three common threads are, first, the types of drivers for reform, that is, how policy change originates, either bottom-up from the institutions, or top-down from the government, and various possibilities in between. Second, understanding challenges to institutional autonomy in a continuum of intensity of state intended intervention in higher education. Third, explaining different levels of strain between public and private sectors in higher education based on conditions of competition for economic resources. While the papers in this special issue do not cover all countries, nor all issues on which policy has been crafted in the last two decades across the region, the collection of articles herein account for topics of enduring importance: faculty work in Ecuador, financial aid in Colombia, public policy decentralization in Argentina, quality assurance models in Colombia and Uruguay, the emerge of new institutions and universities in Argentina and Uruguay, and social justice, access, and inclusion in higher education, in Argentina, Bolivia, Brazil, Chile, Colombia, and Ecuador. The articles presented in this special issue provide much insight onto higher education policy in Latin America and, additionally, offer ample opportunity to develop social science knowledge on the basis of strong comparative work.
Keywords: Change in universities

“Matching Person & Technology (MPT) Model” for Technology Selection as Well as Determination of Usability and Benefit from Use - Martinez, A. P.; Scherer, M. J. (Living in the State of Stuck, 2018)
Technologies have become smarter, smaller, more portable or wearable, and more adaptable. This has led to more choice and, in many cases, complexity in decision-making about selecting the best device and features for a given user. A good match of person and technology requires attention to (a) aspects of and resources in the environments in which the technology will be used, (b) the needs, expectations and preferences of the user, and (c) the functions and features of the technology and service delivery process. If the match is not a quality one from the standpoint of the end user, and the user experience (UX) is not satisfactory, then the technology may go unused, or may not be used optimally. There is a need for an improved person-AT matching and outcomes assessment process because studies and reports show in general that there is a high level of dissatisfaction and nonuse or discard of technology by consumers. Psychologists are uniquely qualified to partner with technology developers in implementing an assessment process that inquires into the potential technology user's predisposition to use a particular technology by addressing, subjective view of current capabilities, view of achievements as well as needs in key life domains of activities and participation, and ratings of fundamental personal factors such as mood status, support from others, engagement in therapy activities and desire to use technology. Utilization of the MPT model and accompanying assessment process has been proven to result in enhanced technology use and goal achievement. Research increasingly highlights the fact that consumers are less likely to use recommended devices when their needs are neither fully addressed nor understood during the technology selection process. A user's perspective of their needs and preferences may be obtained by having them identify and prioritize their desired outcomes and then rate progress in achieving them. This approach was used in developing the Matching Person and Technology measures and has also been used in developing Such a person-centered approach allows outcomes to be measured in reference to changes in a person's satisfaction in achieving desired goals, not merely their functional ability to achieve them. An idiographic evaluation is used (i.e., the person is the unit of analysis and serves as his or her own control), not a normative one (i.e., the person is compared to his or her peers). An idiographic evaluation best captures a consumer-directed and social model perspective of outcomes assessment. Many studies have examined the psychometric qualities and usefulness of the Matching Person and Technology measures. Below is the most recent data on one MPT measure, the Assistive Technology Device Predisposition Assessment (ATD PA), from a study done in the country Greece (Koumpouros et al. 2017; n=115).  Excellent interrater reliability (ICC=0.981, ranging from 0.973-0.987)  Adequate internal consistency (Cronbach's alpha =0.701, ranging from 0.605-0.701)  Adequate-Excellent construct validity for items in the Adaptablility subscale (r=0.537 to 0.783)  Excellent construct validity for items in the Fit to Use subscale (r= 0.691 to 0.801)  Adequate-Excellent construct validity for items in the Socializing (r= 0.498 to 0.767)  Low correlation coefficients between each subscale, indicating subscales measure unique constructs Improvements in person-centered assistive technology services and outcomes assessment are needed, given reports of a high level of dissatisfaction and nonuse of technology by consumers. It is important to ensure an evidence-based, client-centered assessment for determining the match of individuals with the most appropriate technologies for their use. Achieving a desired outcome begins at the point of technology consideration and then progresses to product selection. ABSTRACT Cognitive impairment often results in a range of functional and lifestyle changes for many individuals. This article discusses the development and evolution of a multidisciplinary model of cognitive rehabilitation outpatient practice that integrates technology to improve patient outcomes. The described interdisciplinary treatment approach highlights the need for collaboration by treating providers; focuses on the individual being an active participant in treatment; and discusses the value that assistive technology can bring to cognitive rehabilitation work as it relates to patient success, functional improvement, and implementation of appropriate and patient specific technological strategies.

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

School leadership and early grade reading: Examining the evidence in Zambia - Rakusin, M; Bostock (Cultivating Dynamic Educators: Case Studies in Teacher Behavior Change in Africa and Asia. RTI Press Publication BK-0022-1809., 2018)